How to prepare a removable information sheet
By forming a recessed part on the toner image surface and controlling the flat part area, and using an energy-hardened pressure-sensitive adhesive layer, the problem of insufficient peel strength of the UV-hardened pressure-sensitive adhesive on high-image area printed materials is solved, and stable bonding and reliable re-sticking effect under high humidity conditions is achieved.
Patent Information
- Application Number
- JP2020151851
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-10
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-09-10
AI Technical Summary
In the prior art, UV-hardened pressure-sensitive adhesives have insufficient peeling strength on printed materials with high image area, resulting in the separation of the glue layer due to humidity changes when the image is easily shedded or stored during transportation, which affects the beauty and is difficult to effectively re-stick.
By forming a recessed portion on the surface of the toner image formed on the recording medium, and controlling the area of the flat portion within 200 μm, an energy-hardened pressure-sensitive adhesive layer is used, combined with pressing and wrinkle treatment, ensuring that the image can maintain good adhesion in a high humidity environment.
Stable bonding and reliable re-sticking of images under high image area and high humidity conditions are achieved, ensuring the aesthetics and integrity of the images.
Smart Images

Figure 0007625810000006 
Figure 0007625810000007 
Figure 0007625810000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for making a removable information sheet. [Background technology]
[0002] In recent direct mail, the printed surface on which image information is formed is often attached with a pressure-sensitive adhesive, which can be peeled off when necessary. The pressure-sensitive adhesive used is latex rubber or an ultraviolet-curing pressure-sensitive composition, but in the case of image information with a large image area and high advertising effect, ultraviolet-curing pressure-sensitive compositions are mainly used.
[0003] Recently, information changes have become more frequent, and there is an increase in systems that can output variable information, such as names, point information, etc. There is also a demand for faster print output and reduced costs for plate making such as screen printing, and the demand for on-demand printing is growing rapidly.
[0004] The devices used for on-demand printing are usually electrophotographic or inkjet type, but for output including images with a large image area, the electrophotographic method, which uses toner, is advantageous in terms of productivity and cost. Note that images recorded by the electrophotographic method are reproduced by fixing powder color material called toner to the recording medium with heat.
[0005] Regarding ultraviolet-curable pressure-sensitive compositions (so-called UV varnishes), several commercially available ultraviolet-curable pressure-sensitive compositions are commonly used in offset printing. However, when these commercially available ultraviolet-curable pressure-sensitive compositions are used in electrophotography, satisfactory results are rarely obtained due to the incompatibility between the toner and the ultraviolet-curable composition. Generally, toner is composed of resin, pigment, additives such as silica, wax, etc., which may be one of the factors.
[0006] Patent Document 1 is known as a conventional technique using an ultraviolet-curable pressure-sensitive composition. Patent Document 1 discloses forming a toner image, covering the toner image with an ultraviolet-curable pressure-sensitive composition, and then heating and pressing the toner image. In Patent Document 1, a toner image having a layer of an ultraviolet-curable composition is laminated and pressed while being heated, or pressed and then heated and pressed again, thereby preventing the toner image from breaking. Summary of the Invention [Problem to be solved by the invention]
[0007] However, when a toner image is pressed with the ultraviolet-curable pressure-sensitive composition disclosed in Patent Document 1, the peel strength is insufficient, and it cannot withstand vibration during transportation, or the peel strength is too high, and when it is peeled off again, one of the images peels off. Even if there is no problem immediately after pressing, the adhesive strength may become insufficient or may become too high during storage. In particular, in a toner image with a high area ratio, the ultraviolet-curable pressure-sensitive composition that has partially soaked into the paper may not be cured sufficiently, and when a pressed postcard is produced and peeled off after a few days, the image may peel off.
[0008] Furthermore, when a pressure-bonded postcard made by the conventional technology is stored in a humid environment, the toner image does not break, but the adhesive strength between the toner image surface and the ultraviolet-curable pressure-sensitive composition may decrease. Therefore, when the pressure-bonded postcard is peeled off, a part of the ultraviolet-curable pressure-sensitive composition on the toner image surface sticks to the ultraviolet-curable pressure-sensitive composition on the toner image surface that was attached to it. In this state, the image that is peeled off again is not beautiful enough to be used for direct mail, and rather gives a bad impression of the information. Pressure-bonded postcards need to be re-peelable during the period from when they are posted until they are delivered by mail several days later.
[0009] A double-folded (V-folded) pressure-bonded postcard, for example, as shown on the left side of Fig. 8, is made up of six layers: coated paper 71a, 71b, toner images 72a, 72b, and ultraviolet-curable pressure-sensitive compositions 73a, 73b. When peeling is successful, it will look like the top right of Fig. 8. On the other hand, if the adhesive strength between the toner image 72a and the ultraviolet-curable pressure-sensitive composition 73a, or between the ultraviolet-curable pressure-sensitive composition 73b and the toner image 72b is lower than the adhesive strength between the ultraviolet-curable pressure-sensitive composition 73a and the ultraviolet-curable pressure-sensitive composition 73b, the ultraviolet-curable pressure-sensitive composition will peel off from the toner image and stick to the other ultraviolet-curable pressure-sensitive composition (bottom right of Fig. 8).
[0010] In conventional technology, when a pressure-bonded postcard was peeled off, the peeling of the ultraviolet-curable pressure-sensitive composition from the toner image occurred only partially in so-called solid areas, which are large image areas in each part of the image to be bonded, resulting in a significant deterioration in the gloss of the image surface.
[0011] The present invention has been made in consideration of the above problems in the conventional technology, and has an object to provide a method for producing a removable information sheet which solves various problems associated with removable information sheets using toner images, in particular the problem of partial peeling of a layer formed by curing an energy ray-curable pressure-sensitive composition precursor when the sheet is peeled off, and which has excellent adhesion and removable properties and which provides a removable information sheet with a very clean image when peeled off. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides a method for producing a removable information sheet, comprising: a toner image forming step of forming a toner image on a recording medium using a toner; a coating step of coating an energy ray curable pressure-sensitive composition precursor on the recording medium on which the toner image has been formed to form an energy ray curable pressure-sensitive composition precursor layer; a curing step of irradiating the recording medium on which the energy ray curable pressure-sensitive composition precursor layer has been formed with energy rays to cure the energy ray curable pressure-sensitive composition precursor layer to form an energy ray curable pressure-sensitive composition; and a pressing step of laminating the surfaces on which the energy ray curable pressure-sensitive composition has been formed and pressing them together by a pressing means, wherein the toner image formed in the toner image forming step has a size of a flat area of the toner image measured by the following measurement method of 200 μm or less. The toner image forming step includes a transfer step of transferring a toner image on a photoconductor or an intermediate transfer body to the recording medium, and a fixing step of fixing the toner image transferred to the recording medium, and the transfer step is performed by a transfer bias in which a DC bias is superimposed on an AC bias. It is characterized by: <Measurement method> In the solid portion of the toner image, areas that are 2 μm or more deep from the surface are defined as recesses, and other areas are defined as flat portions of the toner image. A microscopic photograph of the solid portion of the toner image is obtained, and the microscopic photograph is binarized. Circles are drawn within the flat portion of the toner image so as not to overlap the recesses, and the diameter of the largest of the drawn circles is defined as the size of the area of the flat portion of the toner image. Effect of the Invention
[0013] According to the present invention, a method for producing a removable information sheet can be provided which has excellent adhesion and excellent removability and gives a removable information sheet with a very beautiful image when re-peeled. [Brief description of the drawings]
[0014] [Figure 1] 1 is an example of an electron microscope photograph of a solid portion of a toner image. [Diagram 2] This is a binarized image of Figure 1. [Diagram 3] FIG. 3 is a diagram showing the size of a flat area of a toner image in FIG. 2. [Figure 4]This is a diagram showing the Imaging Society of Japan Test Chart No. 7 2008 and its supplementary explanation. [Diagram 5] FIG. 1 illustrates an example of an image forming apparatus. [Figure 6] FIG. 1 is a diagram showing an example of an apparatus for applying and curing an energy ray-curable pressure-sensitive composition precursor. [Figure 7] 13 is a binarized image of another example of an electron microscope photograph of a solid portion of a toner image. [Figure 8] 1A and 1B are diagrams showing an example of a layer structure of a removable information sheet and an example of a state in which the removable information sheet is removed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The method for producing a removable information sheet according to the present invention will be described below with reference to the drawings. Note that the present invention is not limited to the following embodiments, and may be modified within the scope of what a person skilled in the art can imagine, such as other embodiments, additions, modifications, deletions, etc., and any embodiment is within the scope of the present invention as long as it has the functions and effects of the present invention.
[0016] The present inventors have investigated in detail why the adhesion between the ultraviolet-curable pressure-sensitive composition and the image is good in areas with small image areas, and have found that the adhesion between the coated paper and the ultraviolet-curable pressure-sensitive composition is extremely good. In addition, they have found that the adhesion of the ultraviolet-curable pressure-sensitive composition is good even in solid areas, in images with only one toner color of cyan, magenta, yellow, and black, so-called monochrome image areas, but the adhesion of the ultraviolet-curable pressure-sensitive composition is poor in solid areas of so-called multi-color images.
[0017] When the small image area and monochrome image areas where the ultraviolet-curable pressure-sensitive composition had good adhesion were analyzed in detail, it was found that in the small image area areas, there were many areas where the toner image was not present and the coated paper surface was exposed. Since the adhesion between the coated paper and the ultraviolet-curable pressure-sensitive composition was extremely good, even if there were areas where the adhesion between the toner image and the ultraviolet-curable pressure-sensitive composition was slightly poor, these areas were not large, and it was found that the ultraviolet-curable pressure-sensitive composition was held in the areas where the adhesion was good.
[0018] On the other hand, it was found that if the solid portion of the multi-color image had some areas where the adhesion of the ultraviolet-curable pressure-sensitive composition was slightly poor, the adhesion decreased when stored under high humidity conditions, and part of the ultraviolet-curable pressure-sensitive composition peeled off when peeled off again.
[0019] The present inventors have investigated in detail what kind of parts of the solid parts of a multi-color image have not peeled off, because there are parts where a part of the ultraviolet-curable pressure-sensitive composition has not peeled off. The solid parts of a multi-color image are usually formed by laminating two to three particles of toner, which are melted by the heat of fixing to form a layer of a toner image, and the surface of the toner image has a smooth shape. However, even in the solid parts, there are parts on the surface of the toner image where one to three particles of toner are missing. It was found that the parts are recessed compared to the surface of the toner image, and the ultraviolet-curable pressure-sensitive composition precursor enters the recessed parts, improving adhesion due to the anchor effect.
[0020] It was found that the more recessed portions there are compared to the surface of the toner image, and in particular the closer the distance between the recessed portions and other recessed portions, the more adhesiveness can be maintained even when stored under high humidity conditions. In particular, it was found that if the distance between the recessed portions and other recessed portions is 200 μm or less, adhesiveness does not decrease even when stored under high humidity conditions, even in solid areas of a multi-color image, and this led to the present invention.
[0021] That is, the method for producing a removable information sheet of the present invention includes a toner image forming step of forming a toner image on a recording medium using a toner, a coating step of coating an energy ray curable pressure-sensitive composition precursor on the recording medium on which the toner image has been formed to form an energy ray curable pressure-sensitive composition precursor layer, a curing step of irradiating the recording medium on which the energy ray curable pressure-sensitive composition precursor layer has been formed with energy rays to cure the energy ray curable pressure-sensitive composition precursor layer to form an energy ray curable pressure-sensitive composition, and a pressing step of laminating the surfaces on which the energy ray curable pressure-sensitive composition has been formed and pressing them together by a pressing means, and is characterized in that in the toner image formed in the toner image forming step, the size of a region of a flat part of the toner image, as determined by the following measurement method, is 200 μm or less. <Measurement method> In the solid portion of the toner image, areas that are 2 μm or more deep from the surface are defined as recesses, and other areas are defined as flat portions of the toner image. A microscopic photograph of the solid portion of the toner image is obtained, and the microscopic photograph is binarized. Circles are drawn within the flat portion of the toner image so as not to overlap the recesses, and the diameter of the largest of the drawn circles is defined as the size of the area of the flat portion of the toner image.
[0022] <Size of flat area> The size of the flat area of the toner image in the solid part of the multi-color image on the surface of the recording medium obtained in the toner image forming process in the method for producing a removable information sheet of the present invention can be determined according to the following methods ((1) to (3)).
[0023] (1) Micrographs of the solid areas of the multicolor image are taken using an optical microscope, an electron microscope, and a scanning probe microscope (SPM). Figure 1 shows an example of an electron microscope photograph. Compared to the flat areas of the image, the recessed areas are lower in height, so they appear white in Figure 1. In particular, the boundary between the flat areas of the image and the recessed areas can be clearly seen due to the edge effect. Figure 1 is an electron microscope photograph, but the flat areas of the image and the recessed areas can also be clearly distinguished in other microscope photographs.
[0024] The magnification of the micrograph can be any value as long as it is sufficient to measure the size of the flat area of the image. However, if the magnification is too high, only a local flat area of the image will be obtained, so it is desirable to obtain a photograph of an area with at least one side of 500 μm or more.
[0025] (2) The micrograph obtained in (1) above is binarized to clearly show flat and recessed areas of the image. Figure 2 shows the binarized electron micrograph of Figure 1. The black areas in Figure 2 are flat areas of the image, and the white areas are recessed areas. When binarized, areas 2 μm or more deep from the surface become white.
[0026] (3) On the binarized image obtained in (2) above, a circle is drawn in the flat portion of the image, and the diameter of the largest circle that does not overlap with any recess is found, and this value is defined as the size of the area of the flat portion of the toner image. Figure 3 is a diagram showing the size of the area of the flat portion of the toner image in Figure 2. The circle shown in Figure 3 is the largest circle among those drawn on the flat portion of the image. In Figure 3, the size of the area of the flat portion of the toner image is 113 μm.
[0027] As described above, it is desirable to obtain a micrograph of an area with, for example, one side being 500 μm or more. Since the recesses in the solid portion are almost uniformly distributed, a micrograph with one side being 500 μm or more is sufficient, but when using a micrograph with one side smaller than 500 μm, the number of micrographs corresponding to an area with one side being 500 μm or more is used.
[0028] In the recording medium on which an image is formed by the toner image forming process in the method for producing a removable information sheet of the present invention, if the flat area of the toner image in the solid part of the multi-color image is 200 μm or less, the adhesiveness of the energy ray-curable pressure-sensitive composition will not decrease even if the removable information sheet is produced and stored under high humidity conditions.
[0029] One method for checking whether the size of the flat area of a toner image is 200 μm or less is to form an image of the Imaging Society of Japan Test Chart No. 7 2008. The Imaging Society of Japan Test Chart No. 7 2008 and its supplementary explanation are shown in Figure 4.
[0030] When the toner image forming step in the method for producing a removable information sheet of the present invention forms an image of the Japan Imaging Society Test Chart No. 7 2008, the size of the flat area of the toner image is 200 μm or less in the areas on the right side of the image where the blue, green, and red densities are the highest (areas indicated by dashed lines in the figure). Because the flat area of the toner image in these areas is the largest, when the size of the flat area of the toner image in these areas is 200 μm or less, the flat area of the toner image in other areas will always be 200 μm or less.
[0031] If the flat area of the toner image in the highest density area of blue, green, and red on the right side of the image formed using the Japan Imaging Society Test Chart No. 7 2008 is 200 μm or less, the flat area of the toner image in the solid area of other toner images will always be 200 μm or less. Note that it is desirable to check all flat areas of the toner image in the highest density areas of blue, green, and red on the right side of the image formed using the Japan Imaging Society Test Chart No. 7 2008, but it is also possible to check just one of the colors.
[0032] In order to form a toner image so that the size of the flat area of the toner image is 200 μm or less, for example, the image density may be lowered, or the type of voltage applied in the transfer step when forming the toner image may be changed.
[0033] In the toner image formed by the toner image forming process, the size of the flat area of the toner image is not particularly limited, but it is preferable that it is not smaller than 60 μm. Since the ultraviolet-curable pressure-sensitive composition is finally laminated on the toner image, the recesses become almost inconspicuous, but if it is smaller than 60 μm, the density of the entire image becomes thin. In addition, the entire image gives an impression of being rough, which is not preferable.
[0034] Hereinafter, the details of the method for producing the removable information sheet of the present invention will be described together with an example of an image forming apparatus used to carry out the present invention. An example of the image forming apparatus used in this embodiment is shown in FIG.
[0035] The image forming apparatus performing the toner image forming step in this embodiment has, for example, an image carrier, an electrostatic latent image forming unit, a developing unit, a transfer unit, and a fixing unit. The image forming apparatus may have a cleaning unit, and may further have other units appropriately selected as necessary, such as a discharging unit, a recycling unit, a control unit, etc. The image forming apparatus may also have a coating and curing unit in order to perform the coating step described later.
[0036] In the toner image forming process in this embodiment, an electrostatic latent image forming process, a developing process, a transfer process, and a fixing process are performed.
[0037] <Electrostatic latent image forming process and electrostatic latent image forming means> The electrostatic latent image forming step is a step of forming an electrostatic latent image on an image bearing member.
[0038] -Image carrier- The image carrier (sometimes called "electrostatic latent image carrier" or "photoreceptor") is not particularly limited in terms of its material, shape, structure, size, etc., and can be appropriately selected from known ones. For example, a suitable shape is a drum shape, and examples of its material include inorganic photoreceptors such as amorphous silicon and selenium, and organic photoreceptors such as polysilane and phthalopolymethine.
[0039] An image bearing member (photoreceptor) used in an image forming apparatus comprises, for example, a conductive support and at least a photosensitive layer on the conductive support, and may further comprise other layers as necessary.
[0040] The photosensitive layer may be a single layer type in which a charge generating material and a charge transporting material are mixed, a normal layer type in which a charge transporting layer is provided on a charge generating layer, or a reverse layer type in which a charge generating layer is provided on a charge transporting layer. In addition, in order to improve the mechanical strength, abrasion resistance, gas resistance, cleaning properties, etc. of the photoreceptor, a top surface layer may be provided on the photosensitive layer. In addition, an undercoat layer may be provided between the photosensitive layer and the conductive support. In addition, each layer may be added with an appropriate amount of a plasticizer, an antioxidant, a leveling agent, etc., as necessary.
[0041] The conductive support has a volume resistance of 1.0×10 10 There are no particular limitations as long as the material has a conductivity of Ω·cm or less, and it can be appropriately selected according to the purpose. For example, metals such as aluminum, nickel, chromium, nichrome, copper, gold, silver, platinum, etc., or metal oxides such as tin oxide and indium oxide are coated on film-like or cylindrical plastic or paper by vapor deposition or sputtering, or plates of aluminum, aluminum alloy, nickel, stainless steel, etc., and tubes which are made into a drum-like tube by a process such as extrusion or drawing, and then surface-treated by cutting, superfinishing, polishing, etc., can be used.
[0042] The diameter of the drum-shaped support is preferably 20 to 150 mm, more preferably 24 to 100 mm, and even more preferably 28 to 70 mm. If the diameter of the drum-shaped support is less than 20 mm, it may be physically difficult to arrange the processes of charging, exposing, developing, transferring, and cleaning around the drum, and if it exceeds 150 mm, the image forming apparatus may become large. In particular, when the image forming apparatus is a tandem type, it is necessary to mount multiple photoconductors, so the diameter is preferably 70 mm or less, more preferably 60 mm or less.
[0043] Furthermore, an endless nickel belt as disclosed in JP-A-52-36016 or an endless stainless steel belt can also be used as the conductive support.
[0044] The undercoat layer of the photoreceptor may be composed of one layer or multiple layers, and examples thereof include (1) a layer mainly composed of a resin, (2) a layer mainly composed of a white pigment and a resin, and (3) a metal oxide film obtained by chemically or electrochemically oxidizing the surface of a conductive substrate, etc. Among these, a layer mainly composed of a white pigment and a resin is preferred.
[0045] Examples of the white pigment include metal oxides such as titanium oxide, aluminum oxide, zirconium oxide, and zinc oxide. Among these, titanium oxide is particularly preferred because it has an excellent ability to prevent injection of charges from the conductive support.
[0046] Examples of the resin include thermoplastic resins such as polyamide, polyvinyl alcohol, casein, and methyl cellulose, and thermosetting resins such as acrylic, phenol, melamine, alkyd, unsaturated polyester, and epoxy. These may be used alone or in combination of two or more.
[0047] The thickness of the undercoat layer is not particularly limited and can be appropriately selected depending on the purpose, and is preferably 0.1 to 10 μm, more preferably 1 to 5 μm.
[0048] Examples of the charge generating material in the photosensitive layer include organic pigments or dyes such as azo pigments, such as monoazo pigments, bisazo pigments, trisazo pigments, and tetrakisazo pigments, triarylmethane dyes, thiazine dyes, oxazine dyes, xanthene dyes, cyanine dyes, styryl dyes, pyrylium dyes, quinacridone pigments, indigo pigments, perylene pigments, polycyclic quinone pigments, bisbenzimidazole pigments, indathrone pigments, squarylium pigments, and phthalocyanine pigments; and inorganic materials such as selenium, selenium-arsenic, selenium-tellurium, cadmium sulfide, zinc oxide, titanium oxide, and amorphous silicon. These may be used alone or in combination of two or more.
[0049] Examples of the charge transport material in the photosensitive layer include anthracene derivatives, pyrene derivatives, carbazole derivatives, tetrazole derivatives, metallocene derivatives, phenothiazine derivatives, pyrazoline compounds, hydrazone compounds, styryl compounds, styrylhydrazone compounds, enamine compounds, butadiene compounds, distyryl compounds, oxazole compounds, oxadiazole compounds, thiazole compounds, imidazole compounds, triphenylamine derivatives, phenylenediamine derivatives, aminostilbene derivatives, triphenylmethane derivatives, etc. These may be used alone or in combination of two or more.
[0050] The photosensitive layer binder resin used to form the photosensitive layer is electrically insulating, and can be a thermoplastic resin, a thermosetting resin, a photocurable resin, a photoconductive resin, etc. that are known per se. Examples of the photosensitive layer binder resin include thermoplastic resins such as polyvinyl chloride, polyvinylidene chloride, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer, ethylene-vinyl acetate copolymer, polyvinyl butyral, polyvinyl acetal, polyester, phenoxy resin, (meth)acrylic resin, polystyrene, polycarbonate, polyarylate, polysulfone, polyethersulfone, and ABS resin, phenol resin, epoxy resin, urethane resin, melamine resin, isocyanate resin, alkyd resin, silicone resin, and thermosetting resins such as thermosetting acrylic resin, polyvinylcarbazole, polyvinyl anthracene, and polyvinylpyrene. These may be used alone or in combination of two or more.
[0051] Examples of the antioxidant include phenolic compounds, paraphenylenediamines, hydroquinones, organic sulfur compounds, and organic phosphorus compounds. Examples of the phenolic compounds include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,2'-methylene-bis-(4-methyl-6-t-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-t-butylphenol), 4,4'-thiobis-(3-methyl-6-t-butylphenol), 4,4'-butylidenebis-(3- methyl-6-t-butylphenol), 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, tocopherols, etc.
[0052] Examples of the paraphenylenediamines include N-phenyl-N'-isopropyl-p-phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, N-phenyl-N-sec-butyl-p-phenylenediamine, N,N'-di-isopropyl-p-phenylenediamine, and N,N'-dimethyl-N,N'-di-t-butyl-p-phenylenediamine.
[0053] Examples of the hydroquinones include 2,5-di-t-octylhydroquinone, 2,6-didodecylhydroquinone, 2-dodecylhydroquinone, 2-dodecyl-5-chlorohydroquinone, 2-t-octyl-5-methylhydroquinone, and 2-(2-octadecenyl)-5-methylhydroquinone.
[0054] Examples of the organic sulfur compounds include dilauryl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, and ditetradecyl-3,3'-thiodipropionate.
[0055] Examples of the organic phosphorus compounds include triphenylphosphine, tri(nonylphenyl)phosphine, tri(dinonylphenyl)phosphine, tricresylphosphine, and tri(2,4-dibutylphenoxy)phosphine.
[0056] These compounds are known as antioxidants for rubber, plastics, oils and fats, etc., and are readily available commercially.
[0057] The amount of the antioxidant added is preferably 0.01 to 10% by mass based on the total mass of the layer to which it is added.
[0058] As the plasticizer, those commonly used as plasticizers for resins, such as dibutyl phthalate and dioctyl phthalate, can be used as they are, and the appropriate amount used is about 0 to 30 parts by mass per 100 parts by mass of the binder resin for the photosensitive layer.
[0059] A leveling agent may be added to the photosensitive layer. Examples of the leveling agent include silicone oils such as dimethyl silicone oil and methylphenyl silicone oil; and polymers or oligomers having a perfluoroalkyl group on the side chain. The amount of the leveling agent used is preferably 0 to 1 part by mass with respect to 100 parts by mass of the resin.
[0060] -Charging and exposure- Next, the formation of an electrostatic latent image can be performed, for example, by uniformly charging the surface of the image carrier and then exposing the surface to light in an imagewise manner, by the electrostatic latent image forming unit. The electrostatic latent image forming unit includes, for example, at least a charger that uniformly charges the surface of the image carrier and an exposure unit that imagewise exposes the surface of the image carrier.
[0061] The charging can be performed, for example, by applying a voltage to the surface of the image bearing member using the charger.
[0062] The charger is not particularly limited and can be appropriately selected depending on the purpose. For example, a contact charger known per se having a conductive or semiconductive roll, brush, film, rubber blade, etc., and a non-contact charger using corona discharge such as a corotron or scorotron can be mentioned. The charger is preferably one having a voltage application means for applying a voltage having an AC component.
[0063] The exposure can be carried out, for example, by imagewise exposing the surface of the image bearing member using the exposure unit.
[0064] The exposure device is not particularly limited as long as it can expose the surface of the image carrier charged by the charger in the shape of an image to be formed, and can be appropriately selected depending on the purpose. Examples of the exposure device include various exposure devices such as a copying optical system, a rod lens array system, a laser optical system, and a liquid crystal shutter optical system. In the present invention, a backlight system in which exposure is performed imagewise from the back side of the image carrier may be adopted.
[0065] <Developing step and developing means> The developing step is a step of developing the electrostatic latent image with a toner or a developer to form a visualized toner image. The visualized toner image can be formed, for example, by developing the electrostatic latent image with the toner or the developer, and can be performed by the developing unit.
[0066] The developing means is not particularly limited as long as it can develop an image using the toner or the developer, and can be appropriately selected from known developing means. For example, a developing means having at least a developing unit that contains the toner or the developer and can apply the toner or the developer to the electrostatic latent image in a contact or non-contact manner is preferably used.
[0067] -toner- --Average circularity and average particle size-- The toner preferably has an average circularity of 0.90 to 1.00, more preferably 0.93 to 1.00, and even more preferably 0.95 to 0.99, which is the average value of the circularity SR expressed by the following mathematical formula 1. This average circularity is an index of the degree of unevenness of toner particles, and indicates 1.00 when the toner is perfectly spherical, and the more complex the surface shape, the smaller the average circularity value.
[0068] <Formula 1> Circularity SR = (perimeter of a circle having the same area as the projected area of a toner particle) / (perimeter of the projected image of a toner particle)
[0069] When the average circularity is in the range of 0.93 to 1.00, the surface of the toner particles is smooth, and the contact area between the toner particles and the photoconductor is small, resulting in excellent transferability. In addition, since the toner particles have no corners, the stirring torque of the developer in the developing device is small, and the stirring drive is stable, so that abnormal images do not occur. In addition, since there are no angular toner particles in the toner forming the dots, when the toner is pressed against the recording medium during transfer, the pressure is applied uniformly to the entire toner forming the dots, and transfer defects are unlikely to occur. In addition, since the toner particles are not angular, the abrasive force of the toner particles themselves is small, and they do not scratch or wear the surface of the image carrier.
[0070] The circularity SR can be measured, for example, by using a flow type particle image analyzer (FPIA-1000, manufactured by Toa Medical Electronics Co., Ltd.). First, 0.1 to 0.5 ml of a surfactant (preferably an alkylbenzene sulfonate) is added as a dispersant to 100 to 150 ml of water from which solid impurities have been removed in advance in a container, and then about 0.1 to 0.5 g of a measurement sample is added. The suspension in which the sample is dispersed is subjected to a dispersion treatment for about 1 to 3 minutes using an ultrasonic disperser, and the dispersion concentration is set to 3000 to 10000 particles / μl, and the shape and particle size of the toner are measured using the above-mentioned device.
[0071] The mass average particle diameter (D4) of the toner is preferably 3 to 10 μm, more preferably 4 to 8 μm. In this range, the toner particles have a sufficiently small particle diameter for minute latent image dots, so that the dot reproducibility is excellent. If the mass average particle diameter (D4) is less than 3 μm, phenomena such as a decrease in transfer efficiency and a decrease in blade cleaning performance may easily occur, and if it exceeds 10 μm, it may be difficult to prevent scattering of characters or lines.
[0072] The toner preferably has a ratio (D4 / D1) of the mass average particle diameter (D4) to the number average particle diameter (D1) of 1.00 to 1.40, more preferably 1.00 to 1.30. The closer the ratio (D4 / D1) is to 1, the sharper the particle size distribution of the toner is. When (D4 / D1) is in the range of 1.00 to 1.40, selective development due to toner particle diameter does not occur, and image quality is excellent in stability. In addition, since the particle size distribution of the toner is sharp, the triboelectric charge distribution is also sharp, and the occurrence of fogging is suppressed. In addition, when the toner particle diameter is uniform, the toner is developed so that the latent image dots are densely and orderly arranged, and therefore the dot reproducibility is excellent.
[0073] Here, the mass average particle diameter (D4) and particle size distribution of the toner are measured, for example, by the Coulter counter method. Examples of an apparatus for measuring the particle size distribution of toner particles by the Coulter counter method include the Coulter Counter TA-II and Coulter Multisizer II (both manufactured by Coulter).
[0074] First, 0.1 to 5 ml of a surfactant (preferably alkylbenzene sulfonate) is added as a dispersant to 100 to 150 ml of an aqueous electrolyte solution. Here, the electrolyte is a solution prepared by using first-class sodium chloride to prepare an approximately 1% NaCl aqueous solution, and for example, ISOTON-II (manufactured by Coulter) can be used. Then, 2 to 20 mg of a measurement sample is further added. The electrolyte in which the sample is suspended is subjected to a dispersion treatment for approximately 1 to 3 minutes using an ultrasonic disperser, and the volume and number of toner particles or toner are measured using a 100 μm aperture as an aperture with the above-mentioned measuring device, and the volume distribution and number distribution are calculated. From the obtained distribution, the mass average particle diameter (D4) and number average particle diameter (D1) of the toner can be obtained.
[0075] Thirteen channels are used: 2.00 to less than 2.52 μm; 2.52 to less than 3.17 μm; 3.17 to less than 4.00 μm; 4.00 to less than 5.04 μm; 5.04 to less than 6.35 μm; 6.35 to less than 8.00 μm; 8.00 to less than 10.08 μm; 10.08 to less than 12.70 μm; 12.70 to less than 16.00 μm; 16.00 to less than 20.20 μm; 20.20 to less than 25.40 μm; 25.40 to less than 32.00 μm; and 32.00 to less than 40.30 μm, and the target particles are those with diameters of 2.00 μm or more and less than 40.30 μm.
[0076] Such a toner having a substantially spherical shape can be produced by crosslinking and / or elongation reaction of a toner composition containing a polyester prepolymer having a functional group containing a nitrogen atom, a polyester, a colorant, and a release agent in an aqueous medium in the presence of resin particles. The toner produced by this reaction can reduce the occurrence of hot offset by hardening the toner surface, and can prevent the stain on the fixing device from appearing on the image.
[0077] The volume average particle diameter (Dv) of the toner is preferably 4 μm to 10 μm. If it is 4 μm or more, cleaning properties in the development process and transfer efficiency in the transfer process are not impaired, and good image quality can be maintained. If it is 10 μm or less, good fine line reproducibility of the image can be maintained.
[0078] --Toner materials and manufacturing methods-- The toner used in this embodiment contains, for example, a binder resin, a colorant, and a release agent, and may contain other components as necessary.
[0079] The binder resin contained in the toner may be, for example, a polyester prepolymer, a polyester, etc. As the polyester prepolymer, a prepolymer made of a modified polyester resin, the above-mentioned polyester prepolymer having a functional group containing a nitrogen atom, etc. may be used.
[0080] The prepolymer made of modified polyester resin may be a polyester prepolymer (A) having an isocyanate group, and the compound which elongates or crosslinks with the prepolymer may be an amine (B).
[0081] The polyester prepolymer (A) having an isocyanate group may be, for example, a product in which a polyester which is a polycondensation product of a polyol (1) and a polycarboxylic acid (2) and which has an active hydrogen group is further reacted with a polyisocyanate (3).
[0082] Examples of the active hydrogen group contained in the polyester include a hydroxyl group (an alcoholic hydroxyl group and a phenolic hydroxyl group), an amino group, a carboxyl group, and a mercapto group. Among these, an alcoholic hydroxyl group is particularly preferred.
[0083] The polyol (1) includes a diol (1-1) and a trihydric or higher polyol (1-2), and is preferably (1-1) alone or a mixture of (1-1) and a small amount of (1-2).
[0084] Examples of the diol (1-1) include alkylene glycols (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, etc.); alkylene ether glycols (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); alicyclic diols (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.); bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.); alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above alicyclic diols; and alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above bisphenols. Among these, alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols are preferred, and alkylene oxide adducts of bisphenols and combinations of these with alkylene glycols having 2 to 12 carbon atoms are particularly preferred.
[0085] Examples of the trihydric or higher polyol (1-2) include trihydric to octahydric or higher polyhydric aliphatic alcohols (glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc.); trihydric or higher phenols (trisphenol PA, phenol novolac, cresol novolac, etc.); and alkylene oxide adducts of the trihydric or higher polyphenols.
[0086] The polycarboxylic acid (2) includes dicarboxylic acids (2-1) and trivalent or higher polycarboxylic acids (2-2). Among these, (2-1) alone and a mixture of (2-1) and a small amount of (2-2) are preferred.
[0087] Examples of the dicarboxylic acid (2-1) include alkylene dicarboxylic acids (succinic acid, adipic acid, sebacic acid, etc.), alkenylene dicarboxylic acids (maleic acid, fumaric acid, etc.), aromatic dicarboxylic acids (phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc.), etc. Among these, alkenylene dicarboxylic acids having 4 to 20 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms are particularly preferred.
[0088] Examples of the trivalent or higher polycarboxylic acid (2-2) include aromatic polycarboxylic acids having 9 to 20 carbon atoms (trimellitic acid, pyromellitic acid, etc.). The polycarboxylic acid (2) may be an acid anhydride or a lower alkyl ester (methyl ester, ethyl ester, isopropyl ester, etc.) of the above-mentioned compounds, which may be reacted with the polyol (1).
[0089] Regarding the ratio of the polyol (1) to the polycarboxylic acid (2), the equivalent ratio [OH] / [COOH] of the hydroxyl group [OH] to the carboxyl group [COOH] is preferably 2 / 1 to 1 / 1, more preferably 1.5 / 1 to 1 / 1, and further preferably 1.3 / 1 to 1.02 / 1.
[0090] Examples of the polyisocyanate (3) include aliphatic polyisocyanates (tetramethylene diisocyanate, hexamethylene diisocyanate, 2,6-diisocyanatomethyl caproate, etc.); alicyclic polyisocyanates (isophorone diisocyanate, cyclohexylmethane diisocyanate, etc.); aromatic diisocyanates (tolylene diisocyanate, diphenylmethane diisocyanate, etc.); araliphatic diisocyanates (α,α,α',α'-tetramethylxylylene diisocyanate, etc.); isocyanurates; and those obtained by blocking the above polyisocyanates with phenol derivatives, oximes, caprolactams, etc. These may be used alone or in combination of two or more.
[0091] The ratio of the polyisocyanate (3) is preferably an equivalent ratio [NCO] / [OH] of an isocyanate group [NCO] to a hydroxyl group [OH] of a polyester having a hydroxyl group, of 5 / 1 to 1 / 1, more preferably 4 / 1 to 1.2 / 1, and even more preferably 2.5 / 1 to 1.5 / 1. If the [NCO] / [OH] ratio exceeds 5, low-temperature fixing property may deteriorate, and if the molar ratio of [NCO] is less than 1, the urea content in the modified polyester decreases, and hot offset resistance deteriorates.
[0092] The content of the polyisocyanate (3) component in the prepolymer (A) having an isocyanate group at its terminal is preferably 0.5 to 40% by mass, more preferably 1 to 30% by mass, and even more preferably 2 to 20% by mass. If the content is less than 0.5% by mass, hot offset resistance is deteriorated and it is disadvantageous in terms of achieving both heat resistant storage stability and low temperature fixability, whereas if it exceeds 40% by mass, low temperature fixability may be deteriorated.
[0093] The number of isocyanate groups contained per molecule in the prepolymer (A) having an isocyanate group is preferably at least 1 on average, more preferably 1.5 to 3 on average, and even more preferably 1.8 to 2.5 on average. If the number is less than 1 per molecule, the molecular weight of the urea-modified polyester may be low, and the hot offset resistance may be deteriorated.
[0094] Examples of the amines (B) include diamines (B1), trivalent or higher polyamines (B2), amino alcohols (B3), amino mercaptans (B4), amino acids (B5), and blocked amino groups of B1 to B5 (B6).
[0095] Examples of the diamine (B1) include aromatic diamines (phenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, etc.); alicyclic diamines (4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminecyclohexane, isophoronediamine, etc.); and aliphatic diamines (ethylenediamine, tetramethylenediamine, hexamethylenediamine, etc.). Examples of the trivalent or higher polyamine (B2) include diethylenetriamine and triethylenetetramine. Examples of the amino alcohol (B3) include ethanolamine and hydroxyethylaniline. Examples of the amino mercaptans (B4) include aminoethyl mercaptan and aminopropyl mercaptan. The amino acids (B5) include aminopropionic acid, aminocaproic acid, and the like. Examples of compounds (B6) obtained by blocking the amino group of B1 to B5 include ketimine compounds obtained from the amines of B1 to B5 and ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.) and oxazoline compounds. Among these amines (B), preferred are B1 and a mixture of B1 with a small amount of B2.
[0096] Furthermore, if necessary, the molecular weight of the urea-modified polyester can be adjusted by using an elongation terminator. Examples of the elongation terminator include monoamines (diethylamine, dibutylamine, butylamine, laurylamine, etc.) and blocked monoamines (ketimine compounds).
[0097] Regarding the ratio of the amines (B), the equivalent ratio [NCO] / [NHx] of the isocyanate group [NCO] in the prepolymer (A) having an isocyanate group to the amino group [NHx] in the amines (B) is preferably 1 / 2 to 2 / 1, more preferably 1.5 / 1 to 1 / 1.5, and even more preferably 1.2 / 1 to 1 / 1.2. If the [NCO] / [NHx] ratio exceeds 2 or is less than 1 / 2, the molecular weight of the urea-modified polyester (i) decreases, and the hot offset resistance deteriorates.
[0098] In the present invention, the polyester (i) modified with a urea bond may contain a urethane bond together with the urea bond. The molar ratio of the urea bond content to the urethane bond content is preferably 100 / 0 to 10 / 90, more preferably 80 / 20 to 20 / 80, and even more preferably 60 / 40 to 30 / 70. If the molar ratio of the urea bond is less than 10%, the hot offset resistance may deteriorate.
[0099] These reactions produce modified polyesters, particularly urea-modified polyesters (i), used in the toner. The urea-modified polyesters (i) are produced by a one-shot method or a prepolymer method. The mass average molecular weight of the urea-modified polyesters (i) is preferably 10,000 or more, more preferably 20,000 to 10,000,000, and even more preferably 30,000 to 1,000,000. If the mass average molecular weight is less than 10,000, the hot offset resistance may deteriorate.
[0100] The number average molecular weight of the urea-modified polyester is not particularly limited when the unmodified polyester (ii) described below is used, and may be any number average molecular weight that is easy to obtain to obtain the above-mentioned mass average molecular weight. When (i) is used alone, the number average molecular weight is preferably 20,000 or less, more preferably 1,000 to 10,000, and even more preferably 2,000 to 8,000. If the number average molecular weight exceeds 20,000, low-temperature fixability and glossiness when used in a full-color image forming apparatus may be deteriorated.
[0101] In the present invention, the polyester (i) modified by the urea bond can be used alone, and an unmodified polyester (ii) can be used together with the polyester (i) as a binder resin component. The combined use of the (ii) improves low-temperature fixability and glossiness when used in a full-color device, and is therefore more preferable than the use of the polyester (ii) alone. The (ii) may be a polycondensate of a polyol (1) and a polycarboxylic acid (2) similar to the polyester component of the (i), and the preferred ones are the same as those of the (i). In addition, the (ii) may be not only an unmodified polyester, but also one modified by a chemical bond other than a urea bond, for example, modified by a urethane bond. It is preferable that (i) and (ii) are at least partially compatible with each other in terms of low-temperature fixability and hot offset resistance.
[0102] Therefore, it is preferable that the polyester component (i) and (ii) have similar compositions. When (ii) is contained, the mass ratio of (i) to (ii) is preferably 5 / 95 to 80 / 20, more preferably 5 / 95 to 30 / 70, further preferably 5 / 95 to 25 / 75, and particularly preferably 7 / 93 to 20 / 80. If the mass ratio of (i) is less than 5 mass%, the hot offset resistance is deteriorated and it may be disadvantageous in terms of achieving both heat resistant storage stability and low temperature fixability.
[0103] The peak molecular weight of the (ii) is preferably 1,000 to 30,000, more preferably 1,500 to 10,000, and even more preferably 2,000 to 8,000. If the peak molecular weight is less than 1,000, the heat resistant storage stability may deteriorate, and if it exceeds 10,000, the low temperature fixability may deteriorate. The hydroxyl value of the (ii) is preferably 5 or more, more preferably 10 to 120, and even more preferably 20 to 80. If the hydroxyl value is less than 5, it may be disadvantageous in terms of achieving both the heat resistant storage stability and the low temperature fixability. The acid value of the (ii) is preferably 1 to 30, and more preferably 5 to 20. By having an acid value, the toner tends to be negatively charged.
[0104] The glass transition temperature (Tg) of the binder resin is preferably 50 to 70° C., more preferably 55 to 65° C. If the glass transition temperature is less than 50° C., blocking during high-temperature storage of the toner may worsen, and if it exceeds 70° C., low-temperature fixability becomes insufficient. Due to the coexistence of the urea-modified polyester resin, the toner used in the present invention tends to exhibit good heat-resistant storage stability compared to known polyester toners, even if it has a low glass transition point.
[0105] The storage modulus of the binder resin is 10,000 dyne / cm at a measurement frequency of 20 Hz. 2 The temperature (TG') at which this occurs is preferably 100° C. or higher, and more preferably from 110 to 200° C. If the temperature (TG') is lower than 100° C., the hot offset resistance may deteriorate.
[0106] The viscosity of the binder resin is preferably 180° C. or less, more preferably 90 to 160° C., at a temperature (Tη) at which the viscosity becomes 1000 poise at a measurement frequency of 20 Hz. If the temperature (Tη) exceeds 180° C., the low-temperature fixability deteriorates. That is, from the viewpoint of achieving both low-temperature fixability and hot offset resistance, TG' is preferably higher than Tη. In other words, the difference between TG' and Tη (TG'-Tη) is preferably larger than 0° C., more preferably 10° C. or more, and even more preferably 20° C. or more. The upper limit of the difference is not particularly limited. From the viewpoint of achieving both heat-resistant storage stability and low-temperature fixability, the difference between Tη and Tg is preferably 0 to 100° C., more preferably 10 to 90° C., and even more preferably 20 to 80° C.
[0107] The binder resin can be produced by the following method. First, the polyol (1) and the polycarboxylic acid (2) are heated to 150 to 280°C in the presence of a known esterification catalyst such as tetrabutoxy titanate or dibutyltin oxide, and the water generated is distilled off under reduced pressure as necessary to obtain a polyester having hydroxyl groups. Next, this is reacted with polyisocyanate (3) at 40 to 140°C to obtain a prepolymer (A) having an isocyanate group. Furthermore, (A) is reacted with amines (B) at 0 to 140°C to obtain a polyester modified with a urea bond. When reacting (3) and when reacting (A) with (B), a solvent can be used as necessary.
[0108] Examples of solvents that can be used include those that are inactive against isocyanate (3), such as aromatic solvents (toluene, xylene, etc.); ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.); esters (ethyl acetate, etc.); amides (dimethylformamide, dimethylacetamide, etc.), and ethers (tetrahydrofuran, etc.).
[0109] When a polyester (ii) that is not modified with a urea bond is used in combination, (ii) is produced in the same manner as for the polyester having a hydroxyl group, and this is dissolved in the solution after completion of the reaction of (i) and mixed.
[0110] In addition, the binder resin other than the polyester resin is not particularly limited and can be appropriately selected according to the purpose. For example, the binder resin may be a homopolymer of styrene or its substitute such as polystyrene, poly-p-styrene, polyvinyltoluene, styrene-p-chlorostyrene copolymer, styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-methacrylic acid copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-α-chloromethyl methacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl methyl ketone copolymer, styrene-butadiene copolymer, styrene-isopropyl copolymer, styrene-maleic acid ester copolymer, or other styrene-based copolymer, polymethyl methacrylate resin, polybutyl methacrylate resin, polyvinyl chloride resin, polyvinyl acetate resin, polyethylene resin, polyurethane resin, epoxy resin, polyvinyl butyral resin, polyacrylic acid resin, rosin resin, modified rosin resin, terpene resin, phenol resin, aliphatic or aromatic hydrocarbon resin, aromatic petroleum resin, etc. These may be used alone or in combination of two or more. Among these, it is particularly preferable to use polyester resins because of their affinity with the recording medium to which they are fixed.
[0111] The toner used in the present invention can be produced by the following methods, but is not limited thereto.
[0112] The toner may be formed by reacting a dispersion of a prepolymer (A) having an isocyanate group in an aqueous medium with (B), or a previously prepared urea-modified polyester (i) may be used. A method for stably forming a dispersion of the urea-modified polyester (i) and the prepolymer (A) in an aqueous medium includes a method of adding a toner raw material composition of the urea-modified polyester (i) and the prepolymer (A) to the aqueous medium and dispersing the mixture by shear force.
[0113] The prepolymer (A) and other toner compositions (hereinafter sometimes referred to as toner raw materials), such as colorant, colorant master batch, release agent, charge control agent, unmodified polyester resin, etc., may be mixed when forming a dispersion in an aqueous medium, but it is more preferable to mix the toner raw materials in advance and then add the mixture to the aqueous medium to disperse them. In the present invention, other toner raw materials such as colorant, release agent, and charge control agent do not necessarily need to be mixed when forming particles in an aqueous medium, and may be added after forming particles. For example, after forming particles that do not contain a colorant, a colorant can be added by a known dyeing method.
[0114] The aqueous medium may be water alone, or may be used in combination with a solvent miscible with water, such as alcohol (methanol, isopropanol, ethylene glycol, etc.), dimethylformamide, tetrahydrofuran, cellosolves (methyl cellosolve, etc.), and lower ketones (acetone, methyl ethyl ketone, etc.).
[0115] The amount of the aqueous medium used per 100 parts by mass of the toner composition containing the urea-modified polyester (i) and the prepolymer (A) is preferably 50 to 2000 parts by mass, more preferably 100 to 1000 parts by mass. If the amount used is less than 50 parts by mass, the dispersion state of the toner composition is poor, and toner particles of the desired particle size may not be obtained, whereas if the amount used exceeds 2000 parts by mass, it is not economical.
[0116] If necessary, a dispersant can be used, which is preferable in that the particle size distribution becomes sharper and the dispersion is more stable.
[0117] The dispersion method is not particularly limited and can be appropriately selected depending on the purpose. For example, known equipment such as low-speed shear type, high-speed shear type, friction type, high-pressure jet type, and ultrasonic type can be applied. In order to make the particle size of the dispersion 2 to 20 μm, the high-speed shear type is preferable. When using a high-speed shear type dispersing machine, the rotation speed is not particularly limited, but is preferably 1000 to 30000 rpm, and more preferably 5000 to 20000 rpm.
[0118] The dispersion time is not particularly limited, but in the case of a batch method, it is usually 0.1 to 5 minutes. The temperature during dispersion is usually preferably 0 to 150° C., more preferably 40 to 98° C. A higher temperature is preferred in that the viscosity of the dispersion made of the urea-modified polyester (i) and the prepolymer (A) is low and dispersion is easy.
[0119] In the process of synthesizing the urea-modified polyester (i) from the prepolymer (A), the amines (B) may be added before dispersing the toner composition in an aqueous medium to cause a reaction, or the amines (B) may be added after dispersing the toner composition in an aqueous medium to cause a reaction from the particle interface. In this case, the urea-modified polyester is preferentially formed on the surface of the toner produced, and a concentration gradient can be provided inside the particles.
[0120] In the above reaction, it is preferable to use a dispersing agent, if necessary. The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include surfactants, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. These may be used alone or in combination of two or more. Among these, surfactants are preferred.
[0121] Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants.
[0122] Examples of the anionic surfactant include alkylbenzene sulfonates, α-olefin sulfonates, and phosphates. Among these, preferred are those having a fluoroalkyl group.
[0123] Examples of the anionic surfactant having a fluoroalkyl group include fluoroalkyl carboxylic acids having 2 to 10 carbon atoms or metal salts thereof, disodium perfluorooctanesulfonyl glutamate, sodium 3-[omega-fluoroalkyl (carbon number 6 to 11) oxy]-1-alkyl (carbon number 3 to 4) sulfonate, sodium 3-[omega-fluoroalkanoyl (carbon number 6 to 8)-N-ethylamino]-1-propanesulfonate, fluoroalkyl (carbon number 11 to 20) carboxylic acids or metal salts thereof, perfluoroalkyl perfluoroalkyl (carbon number: 7 to 13) or metal salts thereof, perfluoroalkyl (carbon number: 4 to 12)sulfonic acids or metal salts thereof, perfluorooctane sulfonic acid diethanolamide, N-propyl-N-(2-hydroxyethyl)perfluorooctane sulfonamide, perfluoroalkyl (carbon number: 6 to 10)sulfonamidopropyl trimethylammonium salts, perfluoroalkyl (carbon number: 6 to 10)-N-ethylsulfonylglycine salts, and monoperfluoroalkyl (carbon number: 6 to 16)ethyl phosphate esters.
[0124] Examples of commercially available surfactants having a fluoroalkyl group include Surflon S-111, S-112, and S-113 (manufactured by Asahi Glass Co., Ltd.); Fluorad FC-93, FC-95, FC-98, and FC-129 (manufactured by Sumitomo 3M Co., Ltd.); Unidyne DS-101 and DS-102 (manufactured by Daikin Industries, Ltd.); Megafac F-110, F-120, F-113, F-191, F-812, and F-833 (manufactured by Dainippon Ink and Chemicals, Inc.); Ectop EF-102, 103, 104, 105, 112, 123A, 123B, 306A, 501, 201, and 204 (manufactured by To-Chem Products Co., Ltd.); and Futergent F-100 and F150 (manufactured by Neos Co., Ltd.).
[0125] Examples of the cationic surfactant include amine salt type surfactants and quaternary ammonium salt type cationic surfactants. Examples of the amine salt surfactant include alkylamine salts, aminoalcohol fatty acid derivatives, polyamine fatty acid derivatives, and imidazolines. Examples of the quaternary ammonium salt type cationic surfactant include alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, pyridinium salts, alkylisoquinolinium salts, and benzethonium chloride.
[0126] Among the cationic surfactants, there can be mentioned aliphatic primary, secondary or tertiary amine acids having a fluoroalkyl group, aliphatic quaternary ammonium salts such as perfluoroalkyl (having 6 to 10 carbon atoms)sulfonamidopropyltrimethylammonium salts, benzalkonium salts, benzethonium chloride, pyridinium salts, imidazolinium salts, and the like.
[0127] Commercially available examples of the cationic surfactant include Surflon S-121 (manufactured by Asahi Glass Co., Ltd.); Fluorad FC-135 (manufactured by Sumitomo 3M Co., Ltd.); Unidyne DS-202 (manufactured by Daikin Industries, Ltd.), Megafac F-150, F-824 (manufactured by Dainippon Ink and Chemicals, Inc.); Ectop EF-132 (manufactured by Tochem Products Co., Ltd.); and Ftergent F-300 (manufactured by Neos Co., Ltd.).
[0128] Examples of the nonionic surfactant include fatty acid amide derivatives and polyhydric alcohol derivatives.
[0129] Examples of the amphoteric surfactant include alanine, dodecyldi(aminoethyl)glycine, di(octylaminoethyl)glycine, and N-alkyl-N,N-dimethylammonium betaine.
[0130] Examples of the poorly water-soluble inorganic compound dispersant include tricalcium phosphate, calcium carbonate, titanium oxide, colloidal silica, and hydroxyapatite.
[0131] Examples of the polymer protective colloid include acids, (meth)acrylic monomers containing a hydroxyl group, vinyl alcohol or ethers with vinyl alcohol, esters of vinyl alcohol and a compound containing a carboxyl group, amide compounds or methylol compounds thereof, chlorides, homopolymers or copolymers of those having a nitrogen atom or a heterocycle thereof, polyoxyethylenes, celluloses, and the like.
[0132] Examples of the acids include acrylic acid, methacrylic acid, α-cyanoacrylic acid, α-cyanomethacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic acid, and maleic anhydride.
[0133] Examples of the (meth)acrylic monomer containing a hydroxyl group include β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, γ-hydroxypropyl acrylate, γ-hydroxypropyl methacrylate, 3-chloro 2-hydroxypropyl acrylate, 3-chloro-2-hydroxypropyl methacrylate, diethylene glycol monoacrylate, diethylene glycol monomethacrylate, glycerin monoacrylate, glycerin monomethacrylate, N-methylol acrylamide, and N-methylol methacrylamide.
[0134] Examples of the vinyl alcohol or ethers with vinyl alcohol include vinyl methyl ether, vinyl ethyl ether, and vinyl propyl ether.
[0135] Examples of the esters of vinyl alcohol and a compound containing a carboxyl group include vinyl acetate, vinyl propionate, and vinyl butyrate.
[0136] Examples of the amide compounds or methylol compounds thereof include acrylamide, methacrylamide, diacetone acrylamide acid, or methylol compounds thereof.
[0137] Examples of the chlorides include acrylic acid chloride and methacrylic acid chloride.
[0138] Examples of the homopolymer or copolymer having a nitrogen atom or a heterocycle thereof include vinylpyridine, vinylpyrrolidone, vinylimidazole, and ethyleneimine.
[0139] Examples of the polyoxyethylene-based surfactants include polyoxyethylene, polyoxypropylene, polyoxyethylene alkylamines, polyoxypropylene alkylamines, polyoxyethylene alkylamides, polyoxypropylene alkylamides, polyoxyethylene nonylphenyl ether, polyoxyethylene lauryl phenyl ether, polyoxyethylene stearyl phenyl ester, and polyoxyethylene nonylphenyl ester.
[0140] Examples of the celluloses include methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
[0141] In preparing the dispersion, a dispersion stabilizer may be used as necessary. The dispersion stabilizer may be, for example, a calcium phosphate or the like that is soluble in an acid or an alkali.
[0142] When the above-mentioned dispersion stabilizer is used, the calcium phosphate can be removed from the fine particles by dissolving the calcium phosphate with an acid such as hydrochloric acid and then washing with water or by decomposing the calcium phosphate with an enzyme.
[0143] In preparing the dispersion, a catalyst for the elongation reaction or the crosslinking reaction can be used, such as dibutyltin laurate or dioctyltin laurate.
[0144] Furthermore, in order to lower the viscosity of the toner composition, a solvent in which the urea-modified polyester (i) and the prepolymer (A) are soluble can be used. The use of a solvent is preferred in that the particle size distribution becomes sharper. The solvent is preferred in that it is volatile and can be easily removed.
[0145] Examples of the solvent include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, and methyl isobutyl ketone. These may be used alone or in combination of two or more. Among these, aromatic solvents such as toluene and xylene; halogenated hydrocarbons such as methylene chloride, 1,2-dichloroethane, chloroform, and carbon tetrachloride are preferred, and aromatic solvents such as toluene and xylene are more preferred.
[0146] The amount of the solvent used relative to 100 parts by mass of the prepolymer (A) is preferably 0 to 300 parts by mass, more preferably 0 to 100 parts by mass, and further preferably 25 to 70 parts by mass. When a solvent is used, it is removed by heating under normal pressure or reduced pressure after the elongation and / or crosslinking reaction.
[0147] The elongation and / or crosslinking reaction time is selected depending on the reactivity of the combination of the isocyanate group structure of the prepolymer (A) and the amines (B), and is usually preferably 10 minutes to 40 hours, more preferably 2 to 24 hours. The reaction temperature is preferably 0 to 150°C, more preferably 40 to 98°C. Furthermore, a known catalyst can be used as necessary. Specific examples include dibutyltin laurate and dioctyltin laurate.
[0148] In order to remove the organic solvent from the obtained emulsion dispersion, a method can be adopted in which the temperature of the entire system is gradually raised and the organic solvent in the droplets is completely evaporated and removed. It is also possible to spray the emulsion dispersion in a dry atmosphere, completely remove the water-insoluble organic solvent in the droplets to form toner particles, and simultaneously evaporate and remove the aqueous dispersant.
[0149] The drying atmosphere in which the emulsified dispersion is sprayed is generally air, nitrogen, carbon dioxide, a gas obtained by heating combustion gas, etc., and in particular, various air streams heated to a temperature equal to or higher than the boiling point of the highest boiling point solvent used. The desired quality can be obtained sufficiently by short-term treatment with a spray dryer, belt dryer, rotary kiln, etc.
[0150] When the particle size distribution is broad when emulsified and dispersed, and the washing and drying treatments are carried out while maintaining the particle size distribution, the particle size distribution can be adjusted by classification to a desired particle size distribution.
[0151] The classification operation can be performed in liquid using a cyclone, decanter, centrifugation, etc. to remove fine particles. The classification operation can be performed after obtaining a powder after drying, but it is preferable to perform it in liquid in terms of efficiency. The obtained unnecessary fine particles or coarse particles can be returned to the kneading step and used to form particles. In this case, the unnecessary fine particles or coarse particles may be in a wet state. It is preferable to remove as much of the dispersant used as possible from the obtained dispersion liquid, but it is preferable to perform this simultaneously with the classification operation described above.
[0152] The resulting dried toner powder can be mixed with different types of particles such as release agent microparticles, charge control microparticles, fluidizing agent microparticles, and colorant microparticles, or the mixed powder can be subjected to a mechanical impact force to fix and fuse the different types of particles on the surface, thereby preventing the different particles from detaching from the surface of the resulting composite particles.
[0153] Specific means include (1) applying an impact force to the mixture using blades rotating at high speed, and (2) introducing the mixture into a high-velocity air current, accelerating it, and causing particles to collide with each other or composite particles against an appropriate collision plate.
[0154] Examples of equipment include an Ang Mill (manufactured by Hosokawa Micron Corporation), a modified I-type Mill (manufactured by Japan Pneumatic Co., Ltd.) with reduced grinding air pressure, a Hybridization System (manufactured by Nara Machinery Works), a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), and an automatic mortar.
[0155] As the colorant used in the toner, pigments and dyes that have been conventionally used as colorants for toners can be used, and as the colorant, those that exhibit colors such as black, yellow, magenta, cyan, etc. It is preferable to form a full-color image using at least four colors, black, yellow, magenta, and cyan.
[0156] The colorant is not particularly limited and can be appropriately selected from known dyes and pigments according to the purpose.Specifically, carbon black, lamp black, iron black, ultramarine blue, nigrosine dye, aniline blue, phthalocyanine blue, phthalocyanine green, Hansa Yellow G, rhodamine 6C lake, chalco oil blue, chrome yellow, quinacridone red, benzidine yellow, rose bengal, etc. can be used alone or in combination.
[0157] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose. For example, the content is preferably 1 part by mass to 15 parts by mass, and more preferably 3 parts by mass to 10 parts by mass, relative to 100 parts by mass of the toner.
[0158] The colorant may be used as a master batch in which it is combined with a resin. The resin is not particularly limited and can be appropriately selected from known resins according to the purpose. For example, styrene or its substituted polymer, styrene copolymer, polymethyl methacrylate resin, polybutyl methacrylate resin, polyvinyl chloride resin, polyvinyl acetate resin, polyethylene resin, polypropylene resin, polyester resin, epoxy resin, epoxy polyol resin, polyurethane resin, polyamide resin, polyvinyl butyral resin, polyacrylic acid resin, rosin, modified rosin, terpene resin, aliphatic hydrocarbon resin, alicyclic hydrocarbon resin, aromatic petroleum resin, chlorinated paraffin, paraffin, etc. can be mentioned. These may be used alone or in combination of two or more.
[0159] Furthermore, if necessary, toner particles themselves can be made to have magnetic properties by incorporating known magnetic components, such as iron oxides such as ferrite, magnetite, maghemite, metals such as iron, cobalt, nickel, or alloys of these with other metals, either alone or in combination, into the toner particles. These components can also be used as colorant components.
[0160] The content of the magnetic material is not particularly limited and can be appropriately selected depending on the purpose. For example, the content is preferably 10 parts by mass to 200 parts by mass, more preferably 20 parts by mass to 150 parts by mass, relative to 100 parts by mass of the binder resin.
[0161] In addition, the number-average particle diameter of the colorant in the toner used in the present invention is preferably 0.5 μm or less, more preferably 0.4 μm or less, and even more preferably 0.3 μm or less. If the number-average particle diameter exceeds 0.5 μm, the dispersibility of the pigment may not reach a sufficient level, and the desired transparency may not be obtained. On the other hand, a colorant having a minute particle diameter of less than 0.1 μm is sufficiently smaller than the half wavelength of visible light, and therefore is considered not to adversely affect the reflection and absorption characteristics of light. Therefore, the colorant particles having a number-average particle diameter of less than 0.1 μm contribute to good color reproducibility and transparency of an OHP sheet having a fixed image. On the other hand, if a large amount of colorant having a particle diameter of more than 0.5 μm is present, the transmission of incident light is hindered or scattered, and the brightness and color of the projected image of the OHP sheet tends to decrease. Furthermore, if a large amount of colorant having a particle diameter of more than 0.5 μm is present, the colorant may be detached from the surface of the toner particles, causing various problems such as fogging, drum contamination, and cleaning failure.
[0162] The colorants having a number average particle size of more than 0.7 μm preferably account for 10% by number or less, and more preferably 5% by number or less, of the total colorants.
[0163] It is also preferable to knead the colorant together with a part or all of the binder resin after adding a wetting liquid in advance. In this case, the binder resin and the colorant are sufficiently attached to each other initially, and the colorant is more effectively dispersed in the toner particles in the subsequent toner production process. This reduces the dispersed particle size of the colorant, and better transparency can be obtained. The binder resin used in advance kneading can be the resins exemplified as the toner binder resin, but is not limited thereto.
[0164] A specific method for kneading the mixture of the binder resin and the colorant with the wetting liquid in advance includes, for example, a method in which the binder resin, the colorant, and the wetting liquid are mixed in a blender such as a Henschel mixer, and then the resulting mixture is kneaded in a kneader such as a two-roll or three-roll mixer at a temperature lower than the softening temperature of the binder resin.
[0165] As the wetting liquid, a common one can be used while taking into consideration the solubility of the binder resin and the wettability with the colorant. For example, organic solvents such as acetone, toluene, and butanone, and water are preferred from the viewpoint of dispersibility of the colorant. Among these, the use of water is particularly preferred from the viewpoints of environmental consideration and maintaining the dispersion stability of the colorant in the subsequent toner production process.
[0166] According to this manufacturing method, not only does the particle size of the colorant particles contained in the obtained toner become smaller, but the dispersion state of the particles becomes more uniform, so that the color reproducibility of the image projected by an OHP becomes even better.
[0167] The toner contains a wax (releasing agent) in order to provide releasability together with the binder resin and the colorant. The melting point of the wax is preferably 40 to 160° C., more preferably 50 to 120° C. If the melting point is less than 40° C., the heat-resistant storage stability may be adversely affected, and if the melting point is more than 160° C., cold offset may easily occur during fixing at low temperatures.
[0168] The melt viscosity of the wax is preferably 5 to 1000 cps, more preferably 10 to 100 cps, at a temperature 20° C. higher than the melting point. If the melt viscosity exceeds 1000 cps, the effect of improving hot offset resistance and low-temperature fixability may be reduced.
[0169] The content of the wax in the toner is preferably 0 to 40% by mass, more preferably 3 to 30% by mass. If the wax content exceeds 40% by mass, the amount of wax deposited on the image surface after the fixing step becomes too large, which may repel the ultraviolet-curable composition and ultraviolet-curable pressure-sensitive composition described below, or inhibit adhesion at the interface between the toner and the ultraviolet-curable composition and ultraviolet-curable pressure-sensitive composition. In the present invention, even a toner containing wax can be easily removed.
[0170] Examples of the wax include animal-derived wax (beeswax, spermaceti, shellac wax, etc.), plant-derived wax (carnauba wax, Japan wax, rice bran wax, candelilla wax, etc.), mineral-derived wax (montan wax, ozokerite, etc.), petroleum-derived wax (paraffin wax, microcrystalline wax, etc.), and ester waxes in which a long-chain fatty acid having 10 to 12 carbon atoms and an aliphatic alcohol having 8 or more carbon atoms are ester-bonded. Paraffin wax, microcrystalline wax, and ester wax are preferred because they have high release ability and are stable in terms of quality. In particular, ester wax does not excessively inhibit the adhesion of the interface between the ultraviolet-curable composition and the ultraviolet-curable pressure-sensitive composition, so that the adhesion between the toner image and the ultraviolet-curable composition is good, and it is preferred because it has good removability even when stored under high humidity.
[0171] Two or more kinds of wax may be mixed for use. In particular, when waxes having different melting points are mixed, the melting point of the wax as a whole becomes lower, which is preferable since it improves the releasability.
[0172] In order to increase the toner charge amount and the rise of the charge amount, a charge control agent may be added to the toner as necessary. When a colored material is used as the charge control agent, a color change occurs, so a colorless or nearly white material is preferable.
[0173] The charge control agent is not particularly limited, and may be one that imparts either positive or negative chargeability, and may be appropriately selected from known ones according to the purpose. For example, triphenylmethane dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, salicylic acid metal salts, and salicylic acid derivative metal salts can be mentioned.
[0174] The charge control agent can be a commercially available product.The commercially available products include, for example, quaternary ammonium salt Bontron P-51, oxynaphthoic acid metal complex E-82, salicylic acid metal complex E-84, phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.); quaternary ammonium salt molybdenum complex TP-302, TP-415 (all manufactured by Hodogaya Chemical Industry Co., Ltd.); quaternary ammonium salt Copy Charge PSY VP2038, triphenylmethane derivative Copy Blue PR, quaternary ammonium salt Copy Charge NEG VP2036, Copy Charge NX VP434 (all manufactured by Hoechst Co., Ltd.); LRA-901, boron complex LR-147 (all manufactured by Nippon Carrier Co., Ltd.), quinacridone, azo pigment, and other polymeric compounds having functional groups such as sulfonic acid group, carboxyl group, and quaternary ammonium salt.
[0175] The amount of the charge control agent added varies depending on the type of binder resin, the presence or absence of additives, the toner production method including the dispersion method, and the like, and cannot be uniquely defined, but is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the binder resin. If the amount added exceeds 10 parts by mass, the chargeability of the toner becomes too high, reducing the effect of the charge control agent and increasing the electrostatic attraction force with the developing roller, which may lead to a decrease in the fluidity of the developer and a decrease in image density.
[0176] These charge control agents may be melt-kneaded together with the master batch and the resin and then dissolved and dispersed, or may be directly dissolved in an organic solvent and added when dispersing, or may be fixed on the toner surface after the toner particles are produced.
[0177] When the toner composition is dispersed in an aqueous medium during the toner production process, resin fine particles may be added mainly for stabilizing the dispersion.
[0178] The resin fine particles can be any resin that can form an aqueous dispersion, and may be a thermoplastic resin or a thermosetting resin. Examples include vinyl resins, polyurethane resins, epoxy resins, polyester resins, polyamide resins, polyimide resins, silicon resins, phenol resins, melamine resins, urea resins, aniline resins, ionomer resins, and polycarbonate resins. These may be used alone or in combination of two or more. Among these, vinyl resins, polyurethane resins, epoxy resins, polyester resins, or combinations thereof are preferred because they are easy to obtain an aqueous dispersion of fine spherical resin particles.
[0179] The vinyl resin may be, for example, a polymer obtained by homopolymerizing or copolymerizing a vinyl monomer, such as a styrene-(meth)acrylic acid ester resin, a styrene-butadiene copolymer, a (meth)acrylic acid-acrylic acid ester polymer, a styrene-acrylonitrile copolymer, a styrene-maleic anhydride copolymer, or a styrene-(meth)acrylic acid copolymer.
[0180] As an external additive for aiding the fluidity, developability, and chargeability of toner particles, inorganic fine particles are suitable. Examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, and silicon nitride.
[0181] The primary particle diameter of the inorganic fine particles is preferably 5 nm to 2 μm, and more preferably 5 nm to 500 nm. The specific surface area of the inorganic fine particles measured by the BET method is 20 to 500 m. 2 The amount of the inorganic fine particles added to the toner is preferably from 0.01 to 5% by mass, and more preferably from 0.01 to 2.0% by mass.
[0182] Other polymeric fine particles include, for example, polystyrene obtained by soap-free emulsion polymerization, suspension polymerization, or dispersion polymerization, methacrylic acid ester or acrylic acid ester copolymers, polycondensation systems such as silicone, benzoguanamine, and nylon, and polymer particles made of thermosetting resins.
[0183] A fluidizing agent may also be added to the toner. The fluidizing agent is surface-treated to increase hydrophobicity, thereby preventing deterioration of flow characteristics and charging characteristics even under high humidity conditions. Examples of the fluidizing agent include silane coupling agents, silylation agents, silane coupling agents having a fluoroalkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, and modified silicone oils.
[0184] Examples of cleaning improvers for removing the developer remaining on the photoreceptor or intermediate transfer body after transfer include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid; polymer fine particles produced by soap-free emulsion polymerization such as polymethyl methacrylate fine particles and polystyrene fine particles; etc. The polymer fine particles preferably have a relatively narrow particle size distribution and a volume average particle size of 0.01 to 1 μm.
[0185] By using such a toner, it is possible to form a high-quality toner image having excellent development stability, as described above.
[0186] In addition, the image forming apparatus of the present invention can be used not only with the polymerized toner having a structure suitable for obtaining high quality images as described above, but also with a toner of an irregular shape produced by a pulverized method, and in this case, the life of the apparatus can be significantly extended. As the material constituting such a pulverized toner, any material that is normally used as a toner for electrophotography can be used without any particular limitation.
[0187] Examples of the binder resin used in the pulverized toner include homopolymers of styrene or its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene / p-chlorostyrene copolymers, styrene / propylene copolymers, styrene / vinyltoluene copolymers, styrene / vinylnaphthalene copolymers, styrene / methyl acrylate copolymers, styrene / ethyl acrylate copolymers, styrene / butyl acrylate copolymers, styrene / octyl acrylate copolymers, styrene / methyl methacrylate copolymers, styrene / ethyl methacrylate copolymers, styrene / butyl methacrylate copolymers, and styrene / α-chloromethyl methacrylate copolymers. Examples of the resins include styrene copolymers such as styrene / acrylonitrile copolymers, styrene / vinyl methyl ketone copolymers, styrene / butadiene copolymers, styrene / isoprene copolymers, and styrene / maleic acid copolymers; acrylic acid ester homopolymers or copolymers thereof such as polymethyl acrylate, polybutyl acrylate, polymethyl methacrylate, and polybutyl methacrylate; polyvinyl derivatives such as polyvinyl chloride and polyvinyl acetate; polyester polymers, polyurethane polymers, polyamide polymers, polyimide polymers, polyol polymers, epoxy polymers, terpene polymers, aliphatic or alicyclic hydrocarbon resins, and aromatic petroleum resins. These may be used alone or in combination of two or more. Among these, styrene-acrylic copolymer resins, polyester resins, and polyol resins are preferred from the viewpoints of electrical properties and cost, and polyester resins and polyol resins are particularly preferred as resins having good fixing properties.
[0188] In the case of the pulverized toner, the above-mentioned colorant component, wax component, charge control component, etc. are premixed, if necessary, together with these resin components, and then kneaded at a temperature close to or lower than the softening temperature of the resin components, cooled, and then subjected to a pulverization and classification process to produce a toner. In addition, if necessary, the above-mentioned external additive components may be appropriately added and mixed.
[0189] Examples of the melt kneader include a single-screw continuous kneader, a twin-screw continuous kneader, and a batch kneader using a roll mill. For example, a KTK type twin-screw extruder manufactured by Kobe Steel, Ltd., a TEM type extruder manufactured by Toshiba Machine Co., Ltd., a twin-screw extruder manufactured by KCK Co., Ltd., a PCM type twin-screw extruder manufactured by Ikegai Iron Works Co., Ltd., and a co-kneader manufactured by Buss Co., Ltd. are preferably used. This melt kneading is preferably performed under appropriate conditions that do not cause the molecular chain of the binder resin to be cut. Specifically, the melt kneading temperature is performed with reference to the softening point of the binder resin. If the temperature is higher than the softening point, the cutting will be intense, and if the temperature is too low, the dispersion may not proceed.
[0190] In the pulverization, the kneaded material obtained by the kneading is pulverized. In this pulverization, it is preferable to first coarsely pulverize the kneaded material and then finely pulverize it. In this case, a method of pulverizing by colliding with a collision plate in a jet stream, pulverizing by colliding particles with each other in a jet stream, or pulverizing in a narrow gap between a mechanically rotating rotor and a stator is preferably used.
[0191] The classification is performed by classifying the pulverized product obtained by the pulverization to adjust the particles to a predetermined particle size. The classification can be performed by removing fine particles using, for example, a cyclone, a decanter, or a centrifugal separator.
[0192] After the above-mentioned pulverization and classification are completed, the pulverized material is classified in an air current by centrifugal force or the like to produce a toner having a predetermined particle size.
[0193] Alternatively, the toner can be produced by a suspension polymerization method or an emulsion polymerization method.
[0194] In the suspension polymerization method, a colorant, wax, etc. are dispersed in an oil-soluble polymerization initiator and a polymerizable monomer, and the dispersion is emulsified and dispersed in an aqueous medium containing a surfactant, other solid dispersants, etc. by an emulsification method described later. Then, a polymerization reaction is carried out to form particles, and the toner is obtained.
[0195] As the polymerizable monomer, for example, acids such as acrylic acid, methacrylic acid, α-cyanoacrylic acid, α-cyanomethacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic acid, or maleic anhydride, acrylamide, methacrylamide, diacetone acrylamide, or methylol compounds thereof, vinylpyridine, vinylpyrrolidone, vinylimidazole, ethyleneimine, dimethylaminoethyl methacrylate, or other acrylates or methacrylates having an amino group can be used in part to introduce a functional group onto the toner particle surface.
[0196] Furthermore, by selecting a dispersant having an acid group or a basic group as the dispersant to be used, the dispersant can be adsorbed and left on the toner surface, and functional groups can be introduced.
[0197] In the emulsion polymerization method, a water-soluble polymerization initiator and a polymerizable monomer are emulsified in water using a surfactant, and a latex is synthesized by a normal emulsion polymerization method. A dispersion in which a colorant, wax, etc. are separately dispersed in an aqueous medium is prepared, and after mixing, the dispersion is aggregated to a toner size and heat-fused to obtain a toner. If a monomer similar to that used in the suspension polymerization method is used as the latex, a functional group can be introduced onto the toner surface.
[0198] -Developer- The developing device may be of a dry developing system or a wet developing system, and may be a single-color developing device or a multi-color developing device. For example, a developing device having an agitator that frictionally agitates the toner or the developer to charge it, and a rotatable magnet roller, etc., may be preferably used.
[0199] In the developing unit, for example, the toner and the carrier are mixed and stirred, and the toner becomes charged by friction during this process and is held in a standing state on the surface of a rotating magnet roller, forming a magnetic brush.
[0200] Since the magnet roller is disposed near the image carrier (photoconductor), a part of the toner constituting the magnetic brush formed on the surface of the magnet roller moves to the surface of the image carrier (photoconductor) by electrical attraction, and as a result, the electrostatic latent image is developed by the toner, and a visible image (toner image) is formed by the toner on the surface of the image carrier (photoconductor).
[0201] The developer contained in the developing device is a developer containing the toner, and the developer may be a one-component developer or a two-component developer.
[0202] <Transfer process and transfer means> The transfer step is a step of transferring the toner image onto a recording medium. Although not particularly limited, a preferred embodiment is one in which an intermediate transfer body is used, a toner image is primarily transferred onto the intermediate transfer body, and then the toner image is secondarily transferred onto the recording medium. A more preferred embodiment is one in which two or more colors, preferably a full-color toner, are used as the toner, and the toner image is transferred onto the intermediate transfer body to form a composite transfer image, and a second transfer step is transferred onto the recording medium.
[0203] The transfer can be performed, for example, by charging the image carrier (photoconductor) with the toner image using a transfer charger, and can be performed by the transfer unit. The transfer means preferably has a primary transfer means for transferring a visible image onto an intermediate transfer body to form a composite transfer image, and a secondary transfer means for transferring the composite transfer image onto a recording medium.
[0204] The intermediate transfer body is not particularly limited and can be appropriately selected from known transfer bodies depending on the purpose. For example, a transfer belt is preferably used.
[0205] The intermediate transfer member has a volume resistance of 1.0×10 5 ~1.0×10 11 It is preferable that the volume resistivity is 1.0×10 5If the resistance is less than Ω·cm, when the toner image is transferred from the photoconductor to the intermediate transfer body, discharge may occur, causing the toner image to be distorted, resulting in a toner dust phenomenon. 11 If the resistivity exceeds Ω·cm, after the toner image is transferred from the intermediate transfer body to a recording medium such as paper, a counter charge of the toner image may remain on the intermediate transfer body and appear as an afterimage on the next image.
[0206] The intermediate transfer body may be, for example, a belt-shaped or cylindrical plastic extrusion-molded product obtained by kneading a metal oxide such as tin oxide or indium oxide, or a conductive particle or a conductive polymer, either alone or in combination, with a thermoplastic resin. Alternatively, the intermediate transfer body on an endless belt may be obtained by adding the above-mentioned conductive particle or conductive polymer to a resin liquid containing a thermocrosslinkable monomer or oligomer, if necessary, and centrifugal molding while heating.
[0207] The intermediate transfer member may be provided with a surface layer, and it is preferable that the resistance is appropriately adjusted using a conductive material.
[0208] The transfer means (the primary transfer means, the secondary transfer means) preferably has at least a transfer device that peels and charges the visible image formed on the image carrier (photoconductor) onto the recording medium. The number of the transfer means may be one or more.
[0209] Examples of the transfer device include a corona transfer device using corona discharge, a transfer belt, a transfer roller, a pressure transfer roller, and an adhesive transfer device.
[0210] In the transfer means, the voltage applied during transfer may be a DC voltage, or an AC voltage in which an AC component is superimposed on a DC component and the polarity of the superimposed bias is alternately switched. This type of transfer is also called AC transfer.
[0211] In particular, in the secondary transfer means, by applying an AC voltage, an appropriate gap is created in the toner image transferred to the recording medium, so that the size of the flat area of the toner image in the solid part of the multi-color image can be made 200 μm or less.
[0212] <Recording Media> The recording medium is not particularly limited and can be appropriately selected from known recording media (recording paper). Considering that it is used as direct mail, the recording medium itself is preferably white, and the recording medium surface is preferably coated paper having a coating layer of a white pigment such as calcium carbonate, talc, or kaolin.
[0213] The size of the white pigment is an average particle size of 0.1 μm or more, preferably 0.5 to 5 μm. If the average particle size of the white pigment is less than 0.1 μm, the strength of the white pigment layer is extremely weak, and the white pigment powder falls off and the white pigment layer cracks severely, and the image is likely to peel off when peeled off again.
[0214] In order to maintain a good appearance of the information sheet, the thickness of the white pigment layer is preferably 1 μm or more, and more preferably 1.5 to 3 μm or more.
[0215] <Fixing process and fixing means> The fixing step is a step of fixing the toner image transferred to the recording medium using the fixing means, and may be performed for each color of toner each time it is transferred to the recording medium, or may be performed simultaneously for each color of toner in a stacked state.
[0216] The fixing means is not particularly limited, and known heating and pressurizing means can be used. Examples of the heating and pressurizing means include a combination of a heating roller and a pressure roller, and a combination of a heating roller, a pressure roller and an endless belt.
[0217] The toner particles are heated and pressed in the fixing means. 3 Pa·s or more 10 4It is preferable that the range is Pa·s or less.
[0218] <Other steps and other means in the toner image forming process> If necessary, the apparatus may have other steps, such as a static elimination step, a cleaning step, a recycling step, a control step, etc. If necessary, the apparatus may have other means, such as a static elimination unit, a cleaning unit, a recycling unit, a control unit, etc.
[0219] The charge removing step is a step of removing electricity by applying a charge removing bias to the image bearing member, and can be suitably performed by a charge removing unit. The charge removing means is not particularly limited as long as it can apply a charge removing bias to the image bearing member, and can be appropriately selected from known charge removers. For example, a charge removing lamp is preferably used.
[0220] The cleaning step is a step of removing the toner remaining on the image bearing member, and can be suitably performed by a cleaning means. The cleaning means is preferably provided downstream of the transfer means and upstream of the charger.
[0221] The cleaning means is not particularly limited as long as it can remove the toner remaining on the image bearing member, and can be appropriately selected from among known cleaners, such as a magnetic brush cleaner, an electrostatic brush cleaner, a magnetic roller cleaner, a blade cleaner, a brush cleaner, and a web cleaner.
[0222] The recycling step is a step of recycling the toner removed in the cleaning step to the developing means, and can be suitably carried out by a recycling means. The recycling means is not particularly limited, and examples thereof include known transport means.
[0223] The control step is a step of controlling each of the steps, and can be suitably performed by a control means. The control means is not particularly limited as long as it can control the movement of each of the means, and can be appropriately selected depending on the purpose. For example, the control means includes devices such as a sequencer and a computer.
[0224] <Coating step and coating means, and curing step and curing means> In the method for producing the removable information sheet of this embodiment, after the toner image forming step, a coating step is performed in which an energy ray curable pressure-sensitive composition precursor is coated on the recording medium on which the toner image is formed to form an energy ray curable pressure-sensitive composition precursor layer, and a curing step is performed in which the recording medium on which the energy ray curable pressure-sensitive composition precursor layer is formed is irradiated with energy rays to cure the energy ray curable pressure-sensitive composition precursor layer to form an energy ray curable pressure-sensitive composition. When the coating step and the curing step are described together, they may be referred to as a coating and curing step, and when the coating means and the curing means are described together, they may be referred to as a coating and curing means.
[0225] In this embodiment, the energy ray-curable pressure-sensitive composition precursor refers to the state before application and the state after application and curing, and the energy ray-curable pressure-sensitive composition precursor layer refers to a layer, film, etc. formed by the energy ray-curable pressure-sensitive composition precursor. In addition, the energy ray-curable pressure-sensitive composition refers to the state in which the energy ray-curable pressure-sensitive composition precursor or the energy ray-curable pressure-sensitive composition precursor layer is irradiated with energy rays and the state in which it is irradiated with energy rays and cured.
[0226] Furthermore, since an example of the energy ray is ultraviolet ray, the energy ray-curable pressure-sensitive composition precursor may be referred to as an ultraviolet ray-curable pressure-sensitive composition precursor, an ultraviolet ray-curable pressure-sensitive composition precursor, an ultraviolet ray-curable varnish composition precursor, etc. Similarly, the energy ray-curable pressure-sensitive composition may be referred to as an ultraviolet ray-curable pressure-sensitive composition, an ultraviolet ray-curable pressure-sensitive composition, an ultraviolet ray-curable varnish composition, etc.
[0227] The ultraviolet-curable pressure-sensitive composition is laminated by applying an ultraviolet-curable pressure-sensitive composition precursor onto the recording medium carrying the toner image at any suitable time after the above-mentioned fixing step and curing it. For example, the ultraviolet-curable composition can be applied and cured immediately after the formation of the toner image, such as in an in-line coating device where printing and overcoating are performed in the same printing device. It can also be applied onto the recording medium carrying the toner image after a short or long delay time after printing, such as in an offline coating device where printing and overcoating are performed in different printing devices. Furthermore, the ultraviolet-curable pressure-sensitive composition can be applied to cover the entire recording medium, the entire toner image, a part of the recording medium, or a part of the toner image. It can provide protection or glossing of the printed surface depending on the implementation application.
[0228] When performing the folding process described below, it is preferable not to apply the ultraviolet-curable pressure-sensitive composition precursor to the folded portion in order to reduce the burden on the folded portion.
[0229] To apply the UV-curable pressure-sensitive composition precursor, liquid film coating equipment can be used, including, for example, roll coaters, flexo coaters, rod coaters, blades, wire bars, air knives, curtain coaters, slide coaters, doctor knives, screen coaters, gravure coaters (e.g., offset gravure coaters), slot coaters, and extrusion coaters, inkjet coaters, etc. Such equipment can be used in known manners, such as, for example, forward and reverse roll coating, offset gravure, curtain coating, lithographic coating, screen coating, gravure coating, and inkjet coating.
[0230] The thickness of the ultraviolet-curable pressure-sensitive composition precursor, i.e., the thickness of the energy-ray-curable pressure-sensitive composition precursor layer, is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 μm to 15 μm. If the thickness of the coating is less than 1 μm, repellency may occur or the gloss may be insufficient, and if it exceeds 15 μm, the texture of the image may be deteriorated.
[0231] After the ultraviolet-curable pressure-sensitive composition precursor is applied, the ultraviolet-curable pressure-sensitive composition precursor is cured. The ultraviolet-curable pressure-sensitive composition precursor can be cured by irradiating it with light (mainly ultraviolet light) from a light source.
[0232] The light source is not particularly limited and can be appropriately selected according to the purpose. For example, low pressure mercury lamp, medium pressure mercury lamp, high pressure mercury lamp, ultra-high pressure mercury lamp, xenon lamp, carbon arc lamp, metal halide lamp, fluorescent lamp, tungsten lamp, argon ion laser, helium cadmium laser, helium neon laser, krypton ion laser, various semiconductor lasers, YAG laser, light emitting diode, CRT light source, plasma light source, electron beam, gamma ray, ArF excimer laser, KrF excimer laser, F2 laser, etc. can be mentioned.
[0233] An example of the coating means is shown in Fig. 6. The coating means in Fig. 6 has a coating roller 2, a metal roller 3, a pressure roller 5, a conveyor belt 6, a tray 7, a light source 8, and a scraper 9. The ultraviolet-curable composition 1 is stored between the coating roller 2 and the metal roller 3.
[0234] The recording medium 4 on which the toner image has been formed passes between the rotating application roller 2 and pressure roller 5 while contacting the application roller 2 and pressure roller 5. At that time, the ultraviolet-curable pressure-sensitive composition precursor 1 on the surface of the application roller 2 is transferred to the recording medium 4, so that the ultraviolet-curable pressure-sensitive composition precursor 1 is applied to the recording medium 4.
[0235] The recording medium 4 coated with the ultraviolet-curable pressure-sensitive composition precursor 1 is conveyed by a conveyor belt 6 and passes under a light source 8. At that time, the ultraviolet-curable pressure-sensitive composition precursor 1 coated on the recording medium 4 is cured by ultraviolet light from the light source 8. Thereafter, the recording medium 4 moves onto a tray 7. Unnecessary ultraviolet-curable pressure-sensitive composition precursor 1 adhering to the pressing roller 5 is removed by a scraper 9. The coating and curing process of the ultraviolet-curable pressure-sensitive composition precursor and the means for coating and curing the ultraviolet-curable pressure-sensitive composition precursor are also similar to those for the ultraviolet-curable composition.
[0236] -UV-curable pressure-sensitive composition precursor- The components contained in the ultraviolet-curable pressure-sensitive composition precursor used in the present invention include a polymerizable oligomer, a polymerizable unsaturated compound, a photopolymerization initiator, a sensitizer, a polymerization inhibitor, a surfactant, and the like.
[0237] --Polymerizable oligomer-- The polymerizable oligomer is not particularly limited and may be appropriately selected depending on the purpose. Examples of the polymerizable oligomer include polyester acrylate, epoxy acrylate, and urethane acrylate.
[0238] The polyester acrylate is not particularly limited and can be appropriately selected depending on the purpose. For example, an acrylic acid ester of a polyester polyol obtained from a polyhydric alcohol and a polybasic acid can be used. The polyester acrylate exhibits excellent reactivity.
[0239] The epoxy acrylate is not particularly limited and can be appropriately selected according to the purpose. For example, there is an epoxy acrylate obtained by reacting bisphenol type epoxy, novolac type epoxy, alicyclic epoxy, etc. with acrylic acid. The epoxy acrylate has excellent hardness, flexibility, and curability.
[0240] The urethane acrylate is not particularly limited and can be appropriately selected depending on the purpose. For example, urethane acrylate obtained by reacting polyester polyol, polyether polyol, etc. with diisocyanate and acrylic acid ester having a hydroxyl group can be mentioned. When the urethane acrylate is used, a flexible and strong film can be obtained.
[0241] The polymerizable oligomers may be used alone or in combination of two or more kinds.
[0242] The content of the polymerizable oligomer in the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and can be appropriately selected according to the purpose. For example, it is preferably 5% by mass to 60% by mass, more preferably 10% by mass to 50% by mass, and particularly preferably 20% by mass to 45% by mass relative to the composition. If the content is less than 5% by mass, curing failure may occur, the viscosity may become too low, and flexibility after curing may be impaired. If it exceeds 60% by mass, adhesion may decrease, or the viscosity may become too high. If the content is within the particularly preferred range, it is advantageous in terms of optimizing the viscosity, curing property, and flexibility and strength of the coating layer of the ultraviolet-curable composition after curing.
[0243] --Polymerizable unsaturated compounds-- The polymerizable unsaturated compound is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polymerizable unsaturated compound include monofunctional polymerizable unsaturated compounds, bifunctional polymerizable unsaturated compounds, trifunctional polymerizable unsaturated compounds, and tetrafunctional or higher functional polymerizable unsaturated compounds.
[0244] Examples of the monofunctional polymerizable unsaturated compound include 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, benzyl acrylate, phenyl glycol monoacrylate, and cyclohexyl acrylate.
[0245] Examples of the bifunctional polymerizable unsaturated compound include 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, tripropylene glycol diacrylate, and tetraethylene glycol diacrylate.
[0246] Examples of the trifunctional polymerizable unsaturated compound include trimethylolpropane triacrylate, pentaerythritol triacrylate, and tris(2-hydroxyethyl)isocyanurate triacrylate.
[0247] Examples of the tetrafunctional or higher polymerizable unsaturated compound include pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hydroxypentaacrylate, and dipentaerythritol hexaacrylate.
[0248] Materials with high melting power include 1,6-hexanediol diacrylate, ethyl carbitol acrylate, and acryloyl morpholine. Since the melting power of each material is different, the amount added needs to be adjusted for each material. However, if there is too little, poor adhesion may occur, and if there is too much, image distortion may occur.
[0249] The polymerizable unsaturated compounds may be used alone or in combination of two or more kinds.
[0250] The content of the polymerizable unsaturated compound in the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and can be appropriately selected according to the purpose. For example, 35% by mass to 90% by mass is preferable, 40% by mass to 85% by mass is more preferable, and 45% by mass to 75% by mass is particularly preferable. If the content is less than 35% by mass, the viscosity may become too high, and if it exceeds 90% by mass, curing failure may occur, the viscosity may become too low, or flexibility after curing may be impaired. If the content is within the particularly preferable range, it is advantageous in terms of optimizing the viscosity, curing property, and the coating layer of the ultraviolet-curable pressure-sensitive composition after curing.
[0251] Multifunctional compounds have a faster curing rate than monofunctional compounds and are suitable for high-speed fixing, but they suffer from large volumetric shrinkage. In the case of polymerizable unsaturated compounds that shrink significantly due to the curing reaction, curling is likely to occur, so it is desirable to use polymerizable unsaturated compounds and their polymers with as little volumetric shrinkage as possible.
[0252] The polymerizable unsaturated compound preferably has a volume shrinkage rate of 15% or less.
[0253] The PII (skin irritation) of the polymerizable unsaturated compound and the polymerizable oligomer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1.0 or less. If the PII exceeds 1.0, the irritation to the skin is too strong, which may cause a safety problem.
[0254] The hues of the polymerizable unsaturated compound and the polymerizable oligomer are preferably as close to colorless and transparent as possible, and the Gardner gray scale is preferably equal to or less than 2. If the Gardner gray scale exceeds 2, the color of the image area may change, and discoloration of the background area may become noticeable.
[0255] --Photopolymerization initiator-- The photopolymerization initiator is not particularly limited and may be appropriately selected depending on the purpose. Examples of the photopolymerization initiator include benzophenone, benzoin ethyl ether, benzoin isopropyl ether, and benzil.
[0256] The photopolymerization initiator may be a commercially available product, such as Irgacure 1300, Irgacure 369, and Irgacure 907 manufactured by Ciba Specialty Chemicals, and Lucirin TPO manufactured by BASF.
[0257] When a mixture of the polymerizable oligomer or the polymerizable unsaturated compound and the photopolymerization initiator is irradiated with ultraviolet light, the photopolymerization initiator generates radicals as shown in the following formulas (I) and (II). The radicals cause an addition reaction to the polymerizable double bond of the polymerizable oligomer or the polymerizable unsaturated compound. Further radicals are generated by the addition reaction, and the addition reaction to the polymerizable double bond of another polymerizable oligomer or the polymerizable unsaturated compound is repeated, thereby progressing the polymerization reaction as shown in the following formula (III).
[0258] (I) Hydrogen abstraction type [ka]
[0259] (II) Photocleavable type [ka]
[0260] (III) Polymerization [ka]
[0261] The photopolymerization initiator is preferably one having good properties such as (i) high ultraviolet light absorption efficiency, (ii) high solubility in the polymerizable oligomer or the polymerizable unsaturated compound, (iii) low odor, yellowing, and toxicity, and (iv) no dark reaction.
[0262] The content of the photopolymerization initiator in the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and can be appropriately selected depending on the purpose. For example, it is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 5% by mass.
[0263] --Sensitizer-- When using the hydrogen abstraction type benzophenone photopolymerization initiator of formula (I) above, the reaction may be slow if the photopolymerization initiator is used alone, so it is preferable to increase the reactivity by using, for example, an amine sensitizer in combination. The inclusion of an amine sensitizer has the effect of supplying hydrogen to the photopolymerization initiator by hydrogen abstraction and the effect of preventing reaction inhibition by oxygen in the air.
[0264] The amine-based sensitizer is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include triethanolamine, triisopropanolamine, 4,4-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, ethyl 4-dimethylaminobenzoate, and isoacyl 4-dimethylaminobenzoate.
[0265] The content of the sensitizer in the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and can be appropriately selected depending on the purpose. For example, the content is preferably 1% by mass to 15% by mass, more preferably 3% by mass to 8% by mass.
[0266] --Polymerization inhibitor-- The polymerization inhibitor is used to enhance the storage stability of the ultraviolet-curable pressure-sensitive composition precursor. The polymerization inhibitor is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polymerization inhibitor include 2,6-di-tert-butyl-p-cresol (BHT), 2,3-dimethyl-6-tert-butylphenol (IA), anthraquinone, hydroquinone (HQ), and hydroquinone monomethyl ether (MEHQ).
[0267] The content of the polymerization inhibitor in the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and may be appropriately selected depending on the purpose, and is preferably, for example, 0.5 to 3% by mass.
[0268] --Surfactant-- By including the surfactant in the ultraviolet-curable pressure-sensitive composition precursor, adsorptivity is imparted to the interface between the toner and the ultraviolet-curable pressure-sensitive composition precursor, and the surface tension of the ultraviolet-curable pressure-sensitive composition precursor is reduced, improving wettability.
[0269] The surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the surfactant include anionic surfactants, nonionic surfactants, silicone surfactants, and fluorosurfactants.
[0270] Examples of the anionic surfactant include sulfosuccinates, disulfonates, phosphates, sulfates, sulfonates, and mixtures thereof. Examples of the nonionic surfactant include polyvinyl alcohol, polyacrylic acid, isopropyl alcohol, acetylene-based diols, ethoxylated octylphenol, ethoxylated branched secondary alcohols, perfluorobutanesulfonates, and alkoxylated alcohols. The silicone surfactant may, for example, be polyether-modified poly-dimethyl-siloxane. The fluorosurfactants include, for example, ethoxylated nonylphenol.
[0271] The content of the surfactant in the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and can be appropriately selected according to the purpose. For example, 0.1% by mass to 5% by mass is preferable, and 0.5% by mass to 3% by mass is more preferable. If the content is less than 0.1% by mass, wettability may not be obtained, and if it exceeds 5% by mass, curability may be inhibited. If the content is within the more preferable range, it is advantageous in terms of improving wettability.
[0272] The other components further include a leveling agent, a matting agent, waxes for adjusting the film properties, and a tackifier (adhesiveness imparting agent) that does not inhibit polymerization and that improves adhesion to recording media such as polyolefin and PET.
[0273] It is also preferable to contain a polymer compatible with the polymerizable oligomer and the polymerizable unsaturated compound. The presence of this polymer prevents the energy ray curable pressure-sensitive composition precursor layer from being destroyed or moved during pressure bonding during the production of the protective sheet, and pressure bonding can be performed reliably. As a preferred polymer, a (meth)acrylic copolymer having a weight average molecular weight of 10,000 to 100,000 and a glass transition temperature of -60°C to 20°C is the most preferred, as it has high compatibility with the polymerizable oligomer and the polymerizable unsaturated compound, good pressure bonding properties, and good removability.
[0274] The (meth)acrylic copolymer in the present invention is obtained by polymerizing a monomer component consisting of an alkyl acrylate or an alkyl methacrylate using an organic solvent as a polymerization solvent.
[0275] Examples of the alkyl acrylate or alkyl methacrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, n-decyl (meth)acrylate, and glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.
[0276] In producing the (meth)acrylic copolymer, if necessary, ethylenically unsaturated monomers copolymerizable with the (meth)acrylic acid ester, for example, carboxylic acid-containing ethylenically unsaturated monomers such as acrylic acid, methacrylic acid, and itaconic acid, and hydroxyalkyl (meth)acrylates, for example, 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and alkylamino (meth)acrylates, for example, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and glycidyl (meth)acrylate, (meth)acrylonitrile, (meth)acrylamide, and other ethylenically unsaturated monomers having functional groups, vinyl acetate, vinyl propionate, styrene, α-methylstyrene, and the like, can be copolymerized.
[0277] As the polymerization solvent for the (meth)acrylic copolymer, various organic solvents can be used, for example, alcohols such as methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, etc.; cellosolves such as cellosolve acetate, methyl cellosolve, ethyl cellosolve, n-butyl cellosolve, i-butyl cellosolve, n-propyl cellosolve, etc.; propylene glycol ethers such as propylene glycol-n-butyl ether, propylene glycol methyl ether, propylene glycol phenyl ether, dipropylene glycol methyl ether, propylene glycol methyl ether acetate, etc.; toluene, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, aromatic (petroleum fraction) solvents, phthalate plasticizers, alkyl phosphate esters, etc.
[0278] When preparing the ultraviolet-curable pressure-sensitive composition precursor, the solution of the (meth)acrylic copolymer (B) dissolved in the solvent may be directly blended, and in this case, the solvent may be finally removed from the composition.
[0279] The (meth)acrylic copolymers synthesized as described above may find particularly useful use within a particular molecular weight range and a particular glass transition temperature range.
[0280] The weight-average molecular weight of the (meth)acrylic copolymer must be 10,000 to 100,000, and preferably 20,000 to 50,000. If the weight-average molecular weight of this component is less than 10,000, the cohesive strength will be insufficient, the adhesiveness will be low, and appropriate removability and adhesiveness may not be obtained.
[0281] Furthermore, when the weight-average molecular weight of this component exceeds 100,000, the compatibility with the polymerizable oligomer and the polymerizable unsaturated compound may decrease. In such a case, a large amount of diluent must be used to blend the component into the polymerizable oligomer and the polymerizable unsaturated compound, which leads to a decrease in the curing speed by ultraviolet light and a decrease in surface gloss, as well as a large problem of hygiene and fire service law due to the deterioration of the working environment caused by the solvent.
[0282] Next, the glass transition temperature of the (meth)acrylic copolymer must be in the range of -60 to 20°C, and is preferably -50 to 10°C. If the glass transition temperature of this component is lower than -60°C, the component may feel sticky and may not provide sufficient adhesive strength. If the glass transition temperature of this component (B) is higher than 20°C, the component may not provide removability or adhesiveness.
[0283] The glass transition temperature in the present invention is the second-order transition point measured for a general polymer, for example, as described in "Acrylic Acid Esters and Their Polymers (II)" by Eizo Ohmori, published by Shokodo Co., Ltd., pages 110 to 115. In the case of a copolymer, it is the calculated glass transition temperature described in the same book, page 120.
[0284] The above (meth)acrylic copolymer has good compatibility with the polymerizable oligomer and the polymerizable unsaturated compound, and it is possible to obtain an ultraviolet-curable varnish composition in which component (B) is uniformly dissolved.
[0285] The blending ratio of the (meth)acrylic copolymer to the polymerizable oligomer and the polymerizable unsaturated compound is not particularly limited. A preferred range is 5 to 80 parts by weight relative to 100 parts by weight of the total of the polymerizable oligomer and the polymerizable unsaturated compound. If the blending ratio is less than 5 parts by weight, the varnish composition may not be provided with sufficient removably adhesive properties or the adhesive properties may be weak. If the blending ratio exceeds 80 parts by weight, the resulting varnish composition may have a strong sticky feel and the inherent gloss of the varnish may be reduced, and the adhesive properties may be too strong at the time of peeling, causing paper tearing, or the blocking resistance of the coated paper may be insufficient.
[0286] The blending ratio (parts by weight) of this component refers to the amount of the copolymer component alone, and does not include the solvent, etc. used in the polymerization.
[0287] In the present invention, the (meth)acrylic copolymer is uniformly dissolved in the composition with other components and is in a solution state, so that the coating surface has excellent gloss and is imparted with blocking resistance under normal living conditions.
[0288] <Crimping step and crimping means, and folding step and folding means> The method for producing a removable information sheet of the present invention includes a pressure-bonding step of bonding the cured surfaces of the energy ray-curable pressure-sensitive composition precursor layers together and bonding them with a pressure-bonding means. The pressure-bonding step is performed by a pressure-bonding means. A folding step may be performed before the pressure-bonding step.
[0289] The physical conditions for lamination can be appropriately selected. The surfaces of the varnish composition coated and cured on the paper surface are brought together, and, for example, a combination of pressure at a linear pressure of about 10 to 50 kg / cm or a linear pressure of about 0.1 to 10 kg / cm and heating at a temperature of 50 to 150° C. can be used. In these cases, the components leach out to the surface, forming an adhesive layer on the surface of the varnish coating layer, enabling re-peelable adhesion between the varnish composition surfaces.
[0290] The adhesive strength can be adjusted as appropriate by selecting the physical conditions and changing the blending ratio of the components, the glass transition temperature, and the average molecular weight; it is weaker than the adhesive strength between the printed surface and the varnished surface, and can provide appropriate releasability without damaging the surface when peeled off.
[0291] The viscosity of the ultraviolet-curable pressure-sensitive composition precursor is not particularly limited and may be appropriately selected depending on the purpose, but the viscosity is preferably 10 mPa·s to 800 mPa·s at 25° C. If the viscosity is less than 10 mPa·s or exceeds 800 mPa·s, it may be difficult to control the coating thickness.
[0292] The viscosity can be measured, for example, by a B-type viscometer (manufactured by Toyo Seiki Seisakusho).
[0293] The ultraviolet-curable pressure-sensitive composition precursor can also be prepared as an oil-based type using a solvent, but an ultraviolet-curable type (photocurable type) using UV is preferred from the viewpoints of ensuring safety, protecting the environment, saving energy, and increasing productivity.
[0294] In the folding process, the recording medium on which the ultraviolet-curable pressure-sensitive composition precursor has been cured is folded in half (V-fold) or in thirds (Z-fold) to bring the surfaces processed with the ultraviolet-curable pressure-sensitive composition together. After being folded in this way, the surfaces are pressed together by a pressing means.
[0295] When using the ultraviolet-curable pressure-sensitive composition, after the coating and curing step, the composition is cut to a desired size as necessary, and a folding step is performed, for example by folding in half or in thirds, and the surfaces processed with the ultraviolet-curable pressure-sensitive composition are joined together. The surfaces processed with the ultraviolet-curable pressure-sensitive composition are bonded together by roller pressure bonding to obtain a removably bonded product. The pressure applied when pressing is generally 50 to 1000 N / cm 2 The range is.
[0296] In this way, by folding and pressing a single sheet, productivity is increased. It is preferable not to apply the ultraviolet-curable pressure-sensitive composition to the folded portion, since this will prevent the folded portion from being damaged when the film is peeled off again.
[0297] The pressing step and the folding step may each be carried out independently a plurality of times.
[0298] <Heating and Pressurizing Step and Heating and Pressurizing Means> In the method for producing a removable information sheet of the present invention, a heating and pressurizing step is provided to completely prevent the toner image from being torn. The heating and pressurizing step is performed downstream of the step of applying and curing the energy ray-curable pressure-sensitive composition precursor. The heating and pressurizing step is also performed after the folding step or the pressing step.
[0299] When the heating and pressing step is performed after the folding step, the pressing step can also serve as the heating and pressing step. In this case, the pressing means presses the recording medium while heating it.
[0300] The heating and pressing step is a step of pressing the laminate in a heated state, and it is preferable from the viewpoint of productivity that the heating and pressing are performed simultaneously. However, this is not limited to this, and in order to make the temperature of the laminate uniform, the laminate may be pressed in a heated state after only heating or after being heated and pressed with a weak force. The heating and pressing step may be performed not only once, but also multiple times. When the heating and pressing step is performed after the pressing step, it can be performed in the same manner as the above-mentioned pressing step.
[0301] The heating and pressurizing step and the heating and pressurizing means may be replaced by the fixing step and the fixing means. For example, after the fixing step, the fixing step is repeated in a manner substituting blank printing (however, since a new developing step or the like is not performed, a phenomenon such as fixing toner or the like does not occur), so that heating and pressurizing can be performed using the same fixing means. Alternatively, the fixing step in an image forming process in which an address is written instead of blank printing may be replaced by this heating and pressurizing step.
[0302] The function of the heating and pressing means may be added to the pressure-bonding step and the pressure-bonding means. However, since the sheet is conveyed via a folding step rather than the fixing step and the fixing means, the heating temperature and the pressure must be set with a margin. Also, when the function of the heating and pressing means is added to the pressure-bonding step and the pressure-bonding means, the amount of pressure is generally much higher than that of the fixing step and the fixing means, so it is necessary to set a balance with the heating temperature.
[0303] If the heating and pressing process is performed simultaneously with the pressure bonding process, the productivity is significantly improved, but since the pressure during the pressure bonding process is very large, the volume expansion of the pressure roller of the pressure bonding device during heating may become a problem, and the maintenance of the device is likely to become complicated. If the heating and pressing process is performed after the pressure bonding process, the pressure is lower than that during the pressure bonding process, so the device is small, low-cost, and highly durable.
[0304] In the heating and pressurizing step, the toner is pressed while being heated to a temperature equal to or higher than the softening temperature of the toner. This increases the strength between the toner image layer and the filler of the paper, and also increases the strength of the coating layer, which is preferable because it allows for good re-peeling.
[0305] <Relationship between wax and the present invention> The adhesion between the toner image and the ultraviolet-curable pressure-sensitive composition is affected by the state of the wax on the surface of the toner image, and it is considered that the higher the coverage of the wax on the surface of the toner image, the worse the adhesion between the toner image and the ultraviolet-curable pressure-sensitive composition. Patent Document 1 specifies the coverage of the wax on the surface of the toner image that provides good image quality and adhesion between the toner image and the ultraviolet-curable pressure-sensitive composition.
[0306] However, when a bonded postcard made with a toner image having a coverage rate of the wax specified in Patent Document 1 is stored in a high humidity environment, the toner image does not break, but the adhesive strength between the surface of the toner image and the ultraviolet-curable pressure-sensitive composition may decrease. In this case, when the bonded postcard is peeled off, a part of the ultraviolet-curable pressure-sensitive composition on the surface of the toner image sticks to the ultraviolet-curable pressure-sensitive composition on the surface of the toner image that was previously attached, which is a problem.
[0307] The present inventors focused on oil-less fixing and conducted detailed investigations into the phenomenon of repelling the energy beam curable pressure-sensitive composition precursor on a toner image that had been oil-less fixed. As a result, it was found that the energy beam curable pressure-sensitive composition precursor was not easily repelled in uniform areas, but was easily repelled in solid areas where there was a toner image and the toner image area was large. Then, the cross section of the solid area of the toner image that had been oil-less fixed was observed with an electron microscope, and it was found that the wax in the toner covered most of the surface of the toner image.
[0308] Furthermore, an energy beam-curable pressure-sensitive composition precursor layer was provided on a toner image that had been subjected to oil-less fixing, and it was found that the energy beam-curable pressure-sensitive composition precursor layer was most likely to peel off in areas where there was a toner image, and particularly in solid areas (especially red, blue, and green areas) where a large amount of toner had adhered. Incidentally, the oil-less fixing here means that fixing is performed without using any lubricant or lubricating oil in the fixing step of the toner image forming process.
[0309] Therefore, the present inventors observed the interface between the solid portion of the toner image that had been oil-less fixed and the energy ray curable pressure-sensitive composition, which had been provided on the solid portion, by an electron microscope. The present inventors found that there were some areas where wax was present at the interface between the solid portion and the energy ray curable pressure-sensitive composition, and that in the areas where the wax was present, there were some areas where the energy ray curable pressure-sensitive composition was slightly floating. In other words, the present inventors found that the more areas where the wax was in contact with the energy ray curable pressure-sensitive composition precursor, the lower the adhesion between the energy ray curable pressure-sensitive composition and the oil-less fixed image.
[0310] From these facts, it is considered that the presence of wax over a wide area on a toner image that has been oil-less fixed inhibits adhesion to the energy beam curable pressure-sensitive composition.Furthermore, it has been found that unless the toner image is an oil-less fixed toner image with a small amount of wax on the surface thereof, it is not possible to provide a highly durable energy beam curable pressure-sensitive composition.
[0311] The present inventors have further studied from another viewpoint. That is, the wax related to the adhesion between the energy ray curable pressure-sensitive composition and the oilless fixed image is distributed on the outermost surface of the oilless fixed image, and the wax present inside the image is not related. Therefore, the inventors have studied whether it is possible to specify an oilless fixed image on which the energy ray curable pressure-sensitive composition can be suitably provided, based on the distribution state of the wax on the outermost surface of the oilless fixed image.
[0312] Here, in a transmission electron microscope (TEM) observation as a method for observing the structure within a polymer, a polymer slice is treated with osmium tetroxide (K. Kato: Polym. Eng. Sci., 7, 38), ruthenium tetroxide (J. S. Trent et al.: Macromolecules, 16, 589), phosphotungstic acid (K. Hess et al.: Kalloid-Z, 168, 37), or the like.
[0313] This is commonly used as a method to add contrast to TEM images, since the way each polymer is chemically modified differs and the chemically modifying substances contain heavy metals, making it difficult for electrons to pass through, so that chemically modified polymers are observed as dark and unmodified polymers are observed as bright. Among these, ruthenium tetroxide is preferred because it can be applied to many polymer materials.
[0314] Toner base particles containing binder resins such as polyester and polystyrene are easily chemically modified with ruthenium tetroxide, while wax is overwhelmingly more difficult to chemically modify with ruthenium tetroxide than toner base particles. Focusing on this, we investigated whether it would be possible to distinguish between areas where wax is present and areas where it is not present in scanning electron microscope (SEM) images by chemically modifying an oil-less fixed image with ruthenium tetroxide. In other words, since Ru, a constituent element of ruthenium tetroxide, has a much higher atomic number than the constituent elements of oil-less fixed images, hydrogen, carbon, nitrogen, and oxygen, it is possible to utilize the characteristic that the amount of reflected electrons or secondary electrons from a sample in an SEM image increases with the atomic number of the element.
[0315] In addition, because ruthenium tetroxide only modifies the outermost surface of a sample, the depth region observed with a scanning electron microscope (SEM) must be as close to the outermost surface as possible. In general, it is known that the observation depth in SEM observation depends on the accelerating voltage, and if the accelerating voltage is 1 kV or less, only information from a depth of a few tens of nm or less can be observed.
[0316] Based on this, the oil-less fixed image was treated with ruthenium tetroxide vapor, and then the surface of the fixed image was observed using reflected electrons with an SEM accelerating voltage of 0.8 kV. It was found that the areas where wax was present appeared dark, and the areas where wax was not present appeared bright.
[0317] Furthermore, it has been discovered that the proportion of the area of the dark parts in this SEM image (reflected electron image) can be treated as the coverage rate of the wax on the outermost surface of the oil-less fixed image, and that the coverage rate of the wax on the outermost surface of the oil-less fixed image can define an oil-less fixed image on which an energy ray-curable pressure-sensitive adhesive can be suitably applied.
[0318] The wax coverage is determined as follows. Using the Japan Imaging Society Test Chart No. 7 2008, at least one fixed solid image of red, green, or blue is exposed to saturated vapor of an aqueous solution of ruthenium tetroxide, and then irradiated with an electron beam at an accelerating voltage of 0.8 kV using a SEM, and the resulting reflected electron image is converted into a binary image consisting of black and white areas. The ratio of the area of the black areas to the area of the entire binary image is determined as the wax coverage.
[0319] In the present invention, the coverage of the wax is preferably 40% to 70%, and more preferably 42% to 65%. When the coverage of the wax is 40% or more, the releasability between the fixing roller and the image is prevented from deteriorating, and a high-quality image can be obtained. When the coverage of the wax is 70% or less, the adhesion of the energy ray-curable pressure-sensitive composition is prevented from deteriorating. Similarly, when a monochrome image is formed by an image forming apparatus which forms a toner image, the wax coverage of the monochrome image is preferably 40% to 70%.
[0320] - Chemical modification treatment - In the method for measuring the coverage of the wax, the concentration of ruthenium tetroxide when the surface of the oilless fixed image is exposed to saturated vapor of the aqueous solution of ruthenium tetroxide may be any concentration as long as the chemical modification of ruthenium tetroxide can be safely and reproducibly performed. For example, it is preferable to use an aqueous solution of 5% by mass of ruthenium tetroxide (e.g., manufactured by TABB (UK)) that is generally sold as an electron microscope reagent, since the chemical modification of ruthenium tetroxide can be stably performed.
[0321] When the ruthenium tetroxide aqueous solution is placed in a sealed space, the ruthenium tetroxide volatilizes and becomes saturated vapor, so that by placing an oilless fixed image in the sealed space, the oilless fixed image can be easily chemically modified with ruthenium tetroxide. Here, the temperature at which the saturated vapor of the ruthenium tetroxide aqueous solution is exposed may be normal room temperature, for example, preferably 15°C to 35°C, and more preferably 18°C to 30°C.
[0322] The time for exposure to the saturated vapor of the ruthenium tetroxide aqueous solution is not particularly limited as long as the oilless fixed image is reliably chemically modified and can be clearly separated from the release agent during SEM observation, but is preferably 3 to 8 minutes, more preferably 4 to 6 minutes. If the exposure time is less than 3 minutes, the oilless fixed image may be insufficiently chemically modified, and it is difficult to clearly separate the release agent from the fixed image, which is not preferable. On the other hand, if the exposure time exceeds 8 minutes, ruthenium tetroxide may adhere to the surface of the release agent, increasing the proportion of dark areas observed in the SEM image, or making the boundary between the area where the release agent is present and the area where it is not present unclear.
[0323] -SEM Observation- When the surface of the oil-less fixed image treated with ruthenium tetroxide is observed by a scanning electron microscope (SEM), the area where the wax is present is observed to be dark, and the area where the wax is not present is observed to be bright. The acceleration voltage at this time is preferably 0.3 kV to 1.0 kV, more preferably 0.5 kV to 0.9 kV. If the acceleration voltage exceeds 1.0 kV, information from a deep part of the oil-less fixed image is detected. Therefore, if the wax is thinly attached, the information of the surface of the oil-less fixed image where ruthenium tetroxide is chemically modified is also picked up through the wax. In the present invention, the area where the wax is present on the outermost surface can be observed with good reproducibility by using an acceleration voltage of 0.8 kV.
[0324] When the oil-less fixed image is treated with ruthenium tetroxide and observed by SEM, the areas where wax is present are dark and the areas where wax is not present are bright in both the secondary electron image and the backscattered electron image, and the backscattered electron image can clearly distinguish the areas where wax is present from the areas where it is not present. This is because the backscattered electrons and the secondary electrons are generated more frequently for elements with larger atomic numbers, but the amount of generated backscattered electrons is more dependent on the atomic number than the secondary electrons. Therefore, the backscattered electron image is preferable because the areas where wax is present are darker and the areas where wax is not present are brighter to the extent that it can eliminate the unevenness information of the oil-less fixed image.
[0325] The magnification for taking the reflected electron image is appropriately selected depending on the state of the wax. Any magnification may be used so long as the image is taken of an area where the toner is present, but a magnification of 100 to 2,000 is preferred.
[0326] The range in which the backscattered electron image is acquired may be an area of 250 μm×250 μm or more, and when a backscattered electron image of an area smaller than this is acquired, the number of backscattered electron images corresponding to the area of 250 μm×250 μm is acquired, and the wax coverage rate described below is calculated. When multiple backscattered electron images are used, the average value of the wax coverage rate is used.
[0327] -Binarization processing- Image processing (binarization) is performed to divide each pixel (or a predetermined number of pixel units) constituting the obtained reflected electron image (image data) into either a part that appears black (black part) or a part that appears white (white part), thereby obtaining a binary image. Examples of binary images obtained by binarizing a reflected electron image are shown in Figures 7(a) and 7(b). Figure 7(a) shows a binary image obtained by binarizing an oil-less fixed image with poor adhesion to an energy beam-curable pressure-sensitive adhesive, and Figure 7(b) shows a binary image obtained by binarizing an oil-less fixed image with good adhesion to an energy beam-curable pressure-sensitive adhesive.
[0328] In binarization, for example, the brightness of each pixel is calculated, and if the brightness is equal to or greater than a certain value (threshold), it is determined as white, and if it is less than the certain value, it is determined as black. The threshold is set with reference to a brightness histogram, but since the image before binarization is almost a binarized image, there is no difficulty in setting the threshold, and even if the threshold is slightly higher or lower, it does not have a large effect on the binarized image.
[0329] -Calculation of the area ratio of Kurobe- Next, the area ratio of the black parts to the entire binary image based on the reflected electron image is calculated. For example, the area ratio may be calculated by calculating the area of the entire binary image and the area of the black parts, and dividing the area of the black parts by the area of the entire binary image, or by dividing the number of pixels (dots) of the black parts by the number of pixels of the entire binary image.
[0330] In the reflected electron image, areas where wax is present appear black, and areas where wax is not present appear white, so the proportion of the area of the black parts in the entire binarized image can be considered as the coverage rate of wax.
[0331] It is preferable to specify the wax coverage rate of the portion with the largest amount of toner adhesion in the oilless fixed image. When an oilless fixing method is adopted, the wax that reduces the adhesion between the energy ray curable pressure sensitive composition and the oilless fixed image is supplied only from the toner. Therefore, the portion with the largest amount of wax in the oilless fixed image is the portion with the largest amount of toner adhesion, i.e., the solid portion of the image.
[0332] In electrophotographic image formation, various colors are reproduced using four colors of toner: black, magenta, cyan, and yellow. Therefore, even in a solid image of an oil-less fixed image, red, blue, and green areas have a larger amount of toner attached than black, and therefore also contain a larger amount of wax.
[0333] To explain again, using the Japan Imaging Society Test Chart No. 7 2008, at least one of the fixed solid images of red, green, and blue is exposed to saturated vapor of an aqueous solution of ruthenium tetroxide. Then, using an electron microscope, an electron beam with an accelerating voltage of 0.8 kV is irradiated, and the resulting reflected electron image is converted into a binary image consisting of black and white parts. The ratio of the area of the black parts to the area of the entire binary image is defined as the wax coverage. If the wax coverage is 40% to 70%, the adhesion to the energy ray-curable pressure-sensitive composition is good, durability is high, and a re-peelable information sheet with a beautiful image and a high-quality feel can be obtained when peeled off.
[0334] The wax coverage varies depending on the wax content, distribution, and type in the toner. The lower the wax content in the toner, the lower the wax coverage, and the more wax in the toner near the toner surface, the higher the wax coverage. In addition, the lower the melting point and the higher the fluidity of the wax used, the higher the wax coverage of the oilless fixed image.
[0335] The wax coverage of the oil-less fixed image also changes depending on the amount of toner attached, and the smaller the amount of toner attached, the lower the wax coverage. Since the image provided with the energy ray curable pressure-sensitive adhesive has a flat image surface, the image appears darker than normal, and the amount of toner attached can be reduced to lower the wax coverage.
[0336] The wax coverage of the oil-less fixed image also changes depending on the fixing conditions. Naturally, the higher the fixing temperature, the longer the heating time by the fixing roller, and the higher the pressure of the fixing roller, the higher the wax coverage of the oil-less fixed image.
[0337] Thus, although there are various factors that change the wax coverage of the oil-less fixed image, once the respective conditions are determined, it is easy to make the wax coverage of the oil-less fixed image approximately constant. A removable information sheet provided with an energy ray-curable pressure-sensitive composition and pressed against the sheet is highly durable, and can provide a beautiful image with a luxurious feel when peeled off. EXAMPLES
[0338] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0339] In the following Examples and Comparative Examples, the weight average molecular weight of the resin, the glass transition temperature of the resin, the isoparaffin content of the wax, and the weight average molecular weight of the wax were analyzed by the methods described below.
[0340] <Weight average molecular weight> The weight average molecular weight of the resin was measured by gel permeation chromatography (GPC). The column was stabilized in a heat chamber at 40°C. Tetrahydrofuran (THF) was passed through the column stabilized at this temperature at a flow rate of 1 mL per minute, and 50 μL to 200 μL of a THF sample solution of the resin, adjusted to a sample concentration of 0.05% by mass to 0.6% by mass, was injected and measured.
[0341] In measuring the molecular weight of the sample, the molecular weight distribution of the sample was calculated from the relationship between the logarithm value and the count number of a calibration curve prepared using several monodisperse polystyrene standard samples. The standard polystyrene samples used for preparing the calibration curve were made of 6×10 2 , 2.1×10 3 , 4×10 3 , 1.75×10 4 , 5.1×10 4 , 1.1×10 5 , 3.9×10 5 , 8.6×10 5 , 2×10 6, 4.48×10 6 It is appropriate to use at least 10 standard polystyrene samples. An RI (refractive index) detector was used.
[0342] <Glass transition temperature> The glass transition temperature of the resin was measured from a DSC curve obtained by differential scanning calorimetry (DSC). The DSC curve was measured using TA-60WS and DSC-60 (manufactured by Shimadzu Corporation) under the measurement conditions shown below.
[0343] [Measurement conditions] Sample container: Aluminum sample pan (with lid) Sample size: 5mg Reference: Aluminum sample pan (10 mg alumina) Atmosphere: Nitrogen (Flow rate: 50mL / min) ·Temperature conditions ·Starting temperature: 20℃ Heating rate: 10℃ / min ·End temperature: 150℃ Hold Time: None ·Cooling temperature: 10℃ / min ·End temperature: 20℃ Hold Time: None Heating rate: 10℃ / min ·End temperature: 150℃
[0344] The measurement results were analyzed using data analysis software TA-60, version 1.52 (manufactured by Shimadzu Corporation). When analyzing the measurement results, a range of ±5°C was specified around the maximum peak of the DrDSC curve, which is the DSC differential curve of the second heating, and the peak temperature was obtained using the peak analysis function of the data analysis software. Next, the maximum endothermic temperature of the DSC curve was obtained using the peak analysis function of the data analysis software in the range of +5°C and -5°C of the peak temperature of the DSC curve. This temperature corresponds to the melting point. In the endothermic peak of the main peak in the temperature range of 40°C to 100°C obtained during the heating process, the intersection of the line at the midpoint of the baseline before and after the endothermic peak appears and the differential thermal curve was taken as the glass transition temperature (Tg).
[0345] <Isoparaffin content in wax and weight average molecular weight of wax> The isoparaffin content (mass%) in the wax and the weight average molecular weight of the wax were measured by the FD (Field Desorption) method using a gas chromatograph TOF mass spectrometer JMS-T100GC "AccuTOF GC" (manufactured by JEOL Ltd.).
[0346] <Resin solution A> A total of 100 parts of monomers consisting of (10 parts of 2-ethylhexyl acrylate, 30 parts of 2-hydroxyl acrylate, 50 parts of butyl methacrylate, and 10 parts of acrylic acid) were added to a 500 ml reaction vessel equipped with a stirrer, a nitrogen gas inlet, a thermometer, and a reflux condenser, 100 parts of isopropyl alcohol as a polymerization solvent, and 1 part of azobisisobutylnitrile as a polymerization initiator, and polymerized at 82°C for 6 hours under reflux of isopropyl alcohol in a nitrogen gas stream to obtain [resin solution A] containing 50% by weight of a transparent and viscous resin component (the (meth)acrylic copolymer used in the present invention). The weight average molecular weight of the obtained resin was 50,000. The glass transition temperature was also -0.1°C.
[0347] <Intermediate Precursor A> 40 parts of Lipoxy SP-1509 (epoxy acrylate oligomer manufactured by Showa Polymer Co., Ltd.), 40 parts of tetraethylene glycol diacrylate, 20 parts of Aronix M-400 (dipentaerythritol hexaacrylate manufactured by Toagosei Co., Ltd.), 5 parts of 2-hydroxy-2-methyl-1-phenyl-propan-1-one (manufactured by BASF), and 0.1 parts of methoquinone were mixed with stirring to obtain [Intermediate Precursor A].
[0348] <Energy ray curable pressure sensitive composition precursor 1> 60 parts of [Resin solution A] was mixed with 105.1 parts of the [Intermediate precursor A] to obtain [Energy ray curable pressure-sensitive composition precursor 1] in a transparent solution state.
[0349] Example 1 <Preparation of Toner 1> [Prescription] Polyester resin (weight average molecular weight Mw: 68,500, glass transition temperature Tg: 65.9°C) 89.5 parts by mass Microcrystalline wax (isoparaffin content: 15% by mass, weight average molecular weight Mw: 645) 5 parts by mass Carbon black (Mitsubishi Chemical Corporation, #44) 5 parts by weight Charge control agent (Spiron Black TR-H, manufactured by Hodogaya Chemical Co., Ltd.) 1 part by weight
[0350] The above formulations were mixed and kneaded at 120°C using a twin-screw extruder (BCTA type, manufactured by Buehler), then pulverized and classified using an airflow pulverizer (jet mill, manufactured by Nisshin Engineering Inc.) to obtain a weight average particle size of 11.0 μm. Then, 2.2 mass% of silica (R-972, manufactured by Nippon Aerosil Co., Ltd.) was mixed using a Henschel mixer (FM type, manufactured by Mitsui Miike Chemical Co., Ltd.) to produce [Black Toner 1].
[0351] [Yellow toner 1] was prepared in the same manner as in the preparation of [Black toner 1] above, except that CI Pigment Yellow 17 was used instead of the carbon black.
[0352] [Magenta toner 1] was prepared in the same manner as in the preparation of [Black toner 1] above, except that CI Pigment Red 57 was used instead of the carbon black.
[0353] [Cyan toner 1] was prepared in the same manner as in the preparation of [Black toner 1] above, except that CI Pigment Blue 15 was used instead of the carbon black.
[0354] The obtained [toner 1] for each of the black, yellow, magenta and cyan colors had an average circularity of 0.90 and a volume average particle size Dv of 6.8 μm.
[0355] <Preparation of Developer 1> A carrier was used in which magnetite particles with a volume average particle size of 50 μm were coated with silicone resin to an average thickness of 0.5 μm, and each of the above-mentioned [Toner 1] colors was mixed so that the toner concentration was 5.0 mass % to prepare [Developer 1] for each of the colors black, yellow, magenta, and cyan.
[0356] <Creating printed matter> On a recording medium of OK topcoat 110kg paper in A4 size, a printout was obtained by outputting the Japan Imaging Society Test Chart No. 7 2008 using [Developer 1] on an imagio MP C7500 manufactured by Ricoh Co., Ltd. Here, a toner image was obtained by oil-less fixing.
[0357] <Measurement of the size of the flat area of the toner image> The blue, green, and red solid areas of the print (the three solid areas surrounded by dashed lines in Figure 4) were cut out, and SEM images were taken using a JEOL field emission scanning microscope JMS-7400F at an acceleration voltage of 3 kV and a magnification of 100x. The size of the flat area of the toner image was measured from the obtained SEM images. The results are shown in Table 2. The flat area of the toner image is the maximum value calculated from the blue, green, and red solid areas of the print.
[0358] <Measurement of wax coverage> The blue, green, and red solid areas of the print were cut out and exposed to saturated vapor of a 5% by mass aqueous solution of ruthenium tetroxide (manufactured by TABB) for 5 minutes to chemically modify the ruthenium tetroxide. Next, a backscattered electron SEM image of the image surface of the chemically modified print was obtained using a transmission electron microscope / scanning electron microscope (manufactured by Garl Zeiss, ULTRA55) at an accelerating voltage of 0.8 kV and a magnification of 1,000 times. The pixels of the obtained backscattered electron SEM image were divided into black and white areas (binarized) using Photoshop (Adobe) to perform image processing to obtain a binary image. The ratio of the area of the black areas to the total area of the binary image (wax coverage) was measured. The results are shown in Table 2. Table 2 shows the maximum wax coverage values obtained from the fixed solid images of red, green, and blue.
[0359] <Creating a removable information sheet> A print was obtained under the same conditions as in the print production process. However, in this case, the image on the left side of the Japan Imaging Society Test Chart No. 7 2008 was printed on two A4 portrait sheets to produce the print. A UV varnish coater (SAC-18E) made by Hirose Iron Works was used to coat the print with 5 to 6 g / cm 2 [Energy ray-curable pressure-sensitive composition precursor 1] was coated on one side to a thickness of 100 nm, and then cured with UV light to form an energy ray-curable pressure-sensitive composition. Next, the image was cut to a width of 150 mm and a length of 150 mm. The two images were placed together with the surfaces that had been surface-treated with [energy ray-curable pressure-sensitive composition precursor 1], and then cut into sheets using a Yuriroll tabletop super calendar with a gauge pressure of 100 N / cm. 2 The specimen was compressed by applying a load of 0.05g. Next, a Yuri Roll tabletop super calendar was used, which was modified to control the roller temperature at 130°C, and the gauge pressure was 50N / cm. 2 In this manner, a removable information sheet was prepared. Two of the above samples were prepared, one was stored in a room environment and the other in an environment of 35°C and 75% humidity for 5 days, and the condition of the image surface when peeled off was observed. In Table 2, the evaluation criteria after re-peeling are as follows. "◎" or "◯" is acceptable.
[0360] [Evaluation Criteria] ◎: Extremely beautiful ○: When observed closely, some of the ultraviolet-curable pressure-sensitive composition has peeled off, but it is at a level suitable for practical use. △: peeling of the ultraviolet-curable composition is evident ×: Image peeling occurs when peeled again
[0361] Comparative Example 1 Samples were prepared in the same manner as in Example 1, except that the classification conditions were changed to [Toner 2] and [Developer 2], the average circularity of the toner was 0.91, and the volume average particle size Dv was 5.6 μm.
[0362] Comparative Example 2 A sample was prepared in the same manner as in Comparative Example 1, except that reheating and compression bonding was not performed.
[0363] Example 2 In Comparative Example 1, a sample was prepared in the same manner as in Comparative Example 1, except that an imagio MP C7500 manufactured by Ricoh Company, Ltd. was modified and the transfer process from the intermediate transfer belt to the coated paper was changed to AC transfer.
[0364] Example 3 In Example 2, samples were prepared in the same manner as in Example 2, except that an ester wax (a mixture of octadecyl docosanoate, eicosanoate, docosyl docosanoate, and octadecyl eicosanoate; mass average molecular weight 620, endothermic peak 70.8°C, half-width 5.3°C) was used as the wax to produce [Toner 3] and [Developer 3].
[0365] Example 4 <Preparation of intermediate precursor B> 10 parts by mass of urethane acrylate oligomer (EBECRYL5129, manufactured by Daicel Cytec Co., Ltd., weight average molecular weight Mw: 800), 41 parts by mass of 1,6-hexanediol diacrylate as a polymerizable unsaturated compound, 10 parts by mass of cyclohexyl acrylate as a polymerizable unsaturated compound, 80 parts by mass of ethyl carbitol acrylate as a polymerizable unsaturated compound, 2.5 parts by mass of ethoxydiethylene glycol acrylate as a polymerizable unsaturated compound, 0.3 parts by mass of hydroquinone monomethyl ether as a polymerization inhibitor, and 6 parts by mass of benzyl (1,2-diphenylethanedione) as a photopolymerization initiator were mixed and stirred at 60°C for 20 minutes to produce [intermediate precursor B].
[0366] <Creating a removable information sheet> A sample was prepared in the same manner as in Example 3, except that [intermediate precursor B] was used instead of [intermediate precursor A] to prepare [energy ray-curable pressure-sensitive composition precursor 2].
[0367] Example 5 <Preparation of intermediate precursor C> 60 parts by mass of polyester acrylate oligomer (EBECRYL1830, manufactured by Daicel Cytec Co., Ltd., weight average molecular weight Mw: 1,500), 30 parts by mass of bisphenol A ethylene oxide adduct diacrylate (V#700, manufactured by Osaka Organic Chemical Co., Ltd.) as a polymerizable unsaturated compound, 5 parts by mass of 2-ethylhexyl acrylate as a polymerizable unsaturated compound, 20 parts by mass of 1,6-hexanediol diacrylate as a polymerizable unsaturated compound, 2.5 parts by mass of ethoxydiethylene glycol acrylate as a polymerizable unsaturated compound, 0.4 parts by mass of 2,6-di-tert-butyl-p-cresol (BHT) as a polymerization inhibitor, and 9 parts by mass of Irgacure 184 (manufactured by Ciba Specialty Chemicals Co., Ltd.) as a photopolymerization initiator were mixed and stirred at 60°C for 20 minutes to obtain [intermediate precursor C].
[0368] <Creating a removable information sheet> A sample was prepared in the same manner as in Example 3, except that [intermediate precursor C] was used in place of [intermediate precursor A] to prepare [energy ray-curable pressure-sensitive composition precursor 3].
[0369] Example 6 <Intermediate Precursor D> 9 parts by mass of pentaerythritol tetraacrylate as a polymerizable unsaturated compound, 2.5 parts by mass of ethoxydiethylene glycol acrylate as a polymerizable unsaturated compound, 30 parts by mass of trimethylolpropane triacrylate as a polymerizable unsaturated compound, and 0.3 parts by mass of hydroquinone as a polymerization inhibitor were placed in a beaker, heated to 120°C while stirring, and 50 parts by mass of diallyl phthalate prepolymer (Daiso DAP 100, manufactured by Daiso Co., Ltd.) were dissolved. Furthermore, 2 parts by mass of aluminum isopropylate dispersed in 2 parts by mass of toluene was gradually added and stirred at 110°C for 20 minutes. During this time, the toluene added as a solvent was removed from the system to obtain a [photocurable varnish base agent]. Next, 70 parts by mass of the [photocurable varnish base agent], 60 parts by mass of 1,6-hexanediol diacrylate as a polymerizable unsaturated compound, 10 parts by mass of benzophenone and 5 parts by mass of p-dimethylaminoacetophenone as photopolymerization initiators, 10 parts by mass of phenyl glycol monoacrylate as a viscosity adjuster, and 4.5 parts by mass of polyoxyethylene glycol alkyl ether as a surfactant were mixed and thoroughly kneaded using a three-roll mill to obtain [intermediate precursor D].
[0370] <Creating a removable information sheet> A sample was prepared in the same manner as in Example 3, except that [intermediate precursor D] was used instead of [intermediate precursor A] to prepare [energy ray-curable pressure-sensitive composition precursor 4].
[0371] Example 7 <Preparation of intermediate precursor E> 60 parts by mass of polyester acrylate oligomer (EBECRYL1830, manufactured by Daicel Cytec Co., Ltd., weight average molecular weight Mw: 1,500), 30 parts by mass of bisphenol A ethylene oxide adduct diacrylate (V#700, manufactured by Osaka Organic Chemical Co., Ltd.) as a polymerizable unsaturated compound, 3 parts by mass of 2-ethylhexyl acrylate as a polymerizable unsaturated compound, 20 parts by mass of 1,6-hexanediol diacrylate as a polymerizable unsaturated compound, 2.5 parts by mass of ethoxydiethylene glycol acrylate as a polymerizable unsaturated compound, 0.4 parts by mass of 2,6-ditert-butyl-p-cresol (BHT) as a polymerization inhibitor, 9 parts by mass of Irgacure 184 (manufactured by Ciba Specialty Chemicals Co., Ltd.) as a photopolymerization initiator, and 2 parts by mass of sodium dialkyl sulfosuccinate as an anionic surfactant were mixed and stirred at 60 ° C. for 20 minutes to obtain [intermediate precursor E].
[0372] <Creating a removable information sheet> A sample was prepared in the same manner as in Example 3, except that [intermediate precursor E] was used instead of [intermediate precursor A] to prepare [energy ray-curable pressure-sensitive composition precursor 5].
[0373] Example 8 <Production of Toner 4> -Synthesis of unmodified polyester (low molecular weight polyester)- Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 67 parts by mass of bisphenol A ethylene oxide 2-mol adduct, 84 parts by mass of bisphenol A propionoxide 3-mol adduct, 274 parts by mass of terephthalic acid, and 2 parts by mass of dibutyltin oxide were charged and reacted under normal pressure at 230°C for 8 hours. Next, the resulting reaction solution was reacted for 6 hours under a reduced pressure of 10 mmHg to 15 mmHg to synthesize an [unmodified polyester]. The resulting [unmodified polyester] had a number average molecular weight (Mn) of 2,200, a weight average molecular weight Mw of 5,700, and a glass transition temperature Tg of 56°C.
[0374] - Preparation of master batch (MB) - 1,000 parts by mass of water, 540 parts by mass of carbon black (Printex35, manufactured by Degussa, DBP oil absorption=42 mL / 100 g, pH=9.5), and 1,200 parts by mass of the unmodified polyester were mixed using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.). The resulting mixture was kneaded with a twin roll at 150° C. for 30 minutes, then cooled by rolling, and pulverized with a pulverizer (manufactured by Hosokawa Micron Corporation) to prepare a [master batch].
[0375] -Synthesis of prepolymer- Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 682 parts by mass of bisphenol A ethylene oxide 2-mol adduct, 81 parts by mass of bisphenol A propylene oxide 2-mol adduct, 283 parts by mass of terephthalic acid, 22 parts by mass of trimellitic anhydride, and 2 parts by mass of dibutyltin oxide were charged and reacted under normal pressure at 230°C for 8 hours. The mixture was then reacted for 5 hours under reduced pressure of 10 mmHg to 15 mmHg to synthesize an intermediate polyester. The intermediate polyester had a number average molecular weight Mn of 2,100, a weight average molecular weight Mw of 9,600, a glass transition temperature Tg of 55°C, an acid value of 0.5 mgKOH / g, and a hydroxyl value of 49 mgKOH / g. Next, 411 parts by mass of the [intermediate polyester], 89 parts by mass of isophorone diisocyanate, and 500 parts by mass of ethyl acetate were charged into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, and reacted at 100° C. for 5 hours to synthesize a [prepolymer] (a modified polyester capable of reacting with an active hydrogen group-containing compound). The free isocyanate content of the obtained [prepolymer] was 1.60% by mass, and the solid content concentration of the [prepolymer] (after standing at 150° C. for 45 minutes) was 50% by mass.
[0376] -Synthesis of ketimines (compounds containing active hydrogen groups)- In a reaction vessel equipped with a stirring bar and a thermometer, 30 parts by mass of isophoronediamine and 70 parts by mass of methyl ethyl ketone were charged and reacted at 50°C for 5 hours to synthesize a [ketimine compound] (a compound containing an active hydrogen group). The amine value of the obtained [ketimine compound] (a compound containing an active hydrogen group) was 423.
[0377] -Synthesis of styrene-acrylic copolymer resin- A reaction tank equipped with a cooling tube, a stirrer, and a nitrogen inlet tube was charged with 300 parts by mass of ethyl acetate, 300 parts by mass of a styrene-acrylic monomer mixture (styrene / 2-ethylhexyl acrylate / acrylic acid / 2-hydroxyethyl acrylate=75 / 15 / 5 / 5), and 10 parts by mass of azobisisobutylnitrile, and the mixture was reacted under normal pressure, nitrogen atmosphere, and 60°C for 15 hours. Next, 200 parts by mass of methanol was added to the reaction liquid, and after stirring for 1 hour, the supernatant was removed and the liquid was dried under reduced pressure to synthesize a [styrene-acrylic copolymer resin].
[0378] - Preparation of toner material solution or dispersion - In a beaker, 10 parts by mass of the [prepolymer], 60 parts by mass of the [unmodified polyester], 130 parts by mass of ethyl acetate, and 30 parts by mass of the [styrene-acrylic copolymer resin] were placed and dissolved by stirring. Next, 2 parts by mass of microcrystalline wax (isoparaffin content: 14.5% by mass, weight average molecular weight Mw: 650), 8 parts by mass of ester wax, and 10 parts by mass of the above-mentioned [master batch] were charged, and a raw material solution was prepared by passing the mixture three times using a bead mill (Ultra Viscomill, manufactured by Imex) under conditions of a liquid feed rate of 1 kg / hour, a disk peripheral speed of 6 m / second, and 80% by volume of zirconia beads having a diameter of 0.5 mm. 2.7 parts by mass of the above-mentioned [ketimine] was added and dissolved, thereby preparing a solution or dispersion of the toner materials.
[0379] - Preparation of aqueous medium phase - An aqueous medium phase was prepared by mixing and stirring 306 parts by mass of ion-exchanged water, 265 parts by mass of a 10% by mass suspension of tricalcium phosphate, and 0.2 parts by mass of sodium dodecylbenzenesulfonate to uniformly dissolve them.
[0380] -Preparation of emulsion or dispersion- 150 parts by weight of the aqueous medium phase was placed in a container and stirred at 12,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), and 100 parts by weight of the solution or dispersion of the toner material was added thereto and mixed for 10 minutes to prepare an emulsion or dispersion (emulsion slurry).
[0381] -Removal of organic solvents- 100 parts by mass of the emulsified slurry was placed in a flask equipped with a stirrer and a thermometer, and the solvent was removed at 30° C. for 12 hours while stirring at a peripheral speed of 20 m / min to obtain a dispersed slurry.
[0382] -Washing and drying- 100 parts by mass of the dispersion slurry was filtered under reduced pressure, and then 100 parts by mass of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. To the obtained filter cake, 300 parts by mass of ion-exchanged water was added, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes) and then filtered. This operation was repeated twice. To the resulting filter cake, 20 parts by mass of a 10% by mass aqueous sodium hydroxide solution was added, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 30 minutes), and then filtered under reduced pressure. To the obtained filter cake, 300 parts by mass of ion-exchanged water was added, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered. To the obtained filter cake, 300 parts by mass of ion-exchanged water was added, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes) and then filtered. This operation was repeated twice. Further, 20 parts by mass of 10% by mass hydrochloric acid was added to the obtained filter cake, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes) and then filtered. To the obtained filter cake, 300 parts by mass of ion-exchanged water was added, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), followed by filtration. This operation was repeated twice to obtain a final filter cake. The resulting final filtered cake was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a 75 μm mesh to obtain [toner base particles].
[0383] -External additive treatment- 100 parts by weight of the obtained [toner base particles] were mixed with 0.6 parts by weight of hydrophobic silica having an average particle size of 100 nm, 1.0 part by weight of titanium oxide having an average particle size of 20 nm, and 0.8 parts by weight of hydrophobic silica fine powder having an average particle size of 15 nm in a Henschel mixer to obtain [Black Toner 4].
[0384] [Yellow Toner 4] was prepared in the same manner as in the preparation of [Black Toner 4] above, except that CI Pigment Yellow 17 was used instead of the carbon black.
[0385] [Magenta Toner 4] was prepared in the same manner as in the preparation of [Black Toner 4] above, except that CI Pigment Red 57 was used instead of the carbon black.
[0386] [Cyan Toner 4] was prepared in the same manner as in the preparation of [Black Toner 4] above, except that CI Pigment Blue 15 was used instead of the carbon black.
[0387] The obtained [Toner 4] for each of the black, yellow, magenta and cyan colors was measured as follows to find that the average circularity was 0.94 and the volume average particle size Dv was 5.7 μm.
[0388] <Production of Developer 4> - Carrier manufacturing - 21.0 parts by mass of acrylic resin solution (toluene solution of cyclohexyl methacrylate / methyl methacrylate = 80 / 20 (mass ratio) copolymer, synthesized from monomers manufactured by Mitsubishi Rayon Co., Ltd., solid content 50 mass%), 6.4 parts by mass of guanamine solution (Super Beckamine TD-126, manufactured by DIC Corporation, solid content 70 mass%), alumina particles (Sumicorundum AA-03, manufactured by Sumitomo Chemical Co., Ltd., average particle size 0.3 μm, specific resistance value 10 14 A coating film-forming solution of acrylic resin and silicone resin containing alumina particles was obtained by dispersing 7.6 parts by mass of alumina silica gel (Ω cm), 65.0 parts by mass of silicone resin solution (SR2410, manufactured by Dow Corning Toray Silicone Co., Ltd., solids content 23 mass%), 1.0 part by mass of aminosilane (SH6020, manufactured by Dow Corning Toray Silicone Co., Ltd., solids content 100 mass%), 60 parts by mass of toluene, and 60 parts by mass of butyl cellosolve for 10 minutes using a homomixer.
[0389] The core material is sintered ferrite powder [(MgO )1.8 (MnO) 49.5 (Fe2O3) 48.0 The coating film forming solution was applied to the surface of the core material to a thickness of 0.15 μm using a Spira Coater (manufactured by Okada Seiko Co., Ltd.), dried, and then the product was left to stand in an electric furnace at 150° C. for 1 hour for firing. After cooling, the product was crushed using a sieve with 106 μm openings to obtain a carrier with a weight average particle size of 35 μm.
[0390] 7 parts by weight of [Toner 4] of each color was mixed uniformly with 100 parts by weight of the carrier using a turbula mixer that rotates the container to mix, and then charged to obtain [Developer 4] of each color.
[0391] <Creating a removable information sheet> A removable information sheet was prepared in the same manner as in Example 3, except that the developer in Example 3 was replaced with the developer 4.
[0392] Example 9 In Example 8, the wax was replaced with 2 parts by mass of microcrystalline wax (isoparaffin content: 14.5% by mass, weight average molecular weight Mw: 650) and 8 parts by mass of ester wax, and 10 parts by mass of ester wax was used to synthesize [Toner 5] and [Developer 5]. The average circularity of the obtained toner was 0.94, and the volume average particle size Dv was 5.7 μm. A sample was prepared in the same manner as in Example 8, except for using this toner.
[0393] Example 10 Samples were prepared in the same manner as in Example 9, except that the synthesized toner was classified to obtain [Toner 6] and [Developer 6] with an average circularity of 0.95 and a volume average particle diameter Dv of 4.8 μm.
[0394] Comparative Example 3 Samples were prepared in the same manner as in Example 10, except that in Example 10, 10 parts by mass of paraffin wax (weight average molecular weight Mw: 500) was used instead of 10 parts by mass of ester wax to produce [Toner 7] and [Developer 7].
[0395] Example 11 A sample was prepared in the same manner as in Example 10, except that the image density was reduced by 6% and image formation was performed.
[0396] Example 12 Using the configuration of Example 9, a direct mail image for a pressure-sensitive postcard (Z-type) for overseas travel was produced. In the same manner as in Example 9, an energy ray-curable pressure-sensitive composition precursor layer was formed, and the energy ray-curable pressure-sensitive composition precursor layer was cured by UV irradiation to form an energy ray-curable pressure-sensitive composition. Thereafter, cutting and folding processes were performed, and the surfaces on which the energy ray-curable pressure-sensitive composition was formed were bonded together, and the product was passed through a heating space in which the roller temperature was controlled to 130°C. Thereafter, the product was passed through a Yuriroll table-top super calendar processed to control the temperature to 130°C, a gauge pressure of 100 N / cm. 2 A load of 1000 was applied and 20 pressure-bonded postcards were produced. The 20 sheets of the produced pressure-bonded postcards were posted in different postboxes in Osaka City and mailed to a business office in Kanagawa Prefecture. When the pressure-bonded postcards arrived at the business office in Kanagawa Prefecture, they were peeled off again, and a very beautiful direct mail image was visible on all of the pressure-bonded postcards.
[0397] The formulations of the energy beam-curable pressure-sensitive composition precursors used in the above Examples and Comparative Examples are shown in Table 1. The values in the table indicate parts by mass. The sample preparation conditions, measurement results, and evaluation results of the above Examples and Comparative Examples are shown in Table 2. In Table 2, "Toner particle size" means the volume average particle size of the toner, and "Mic" means microcrystalline wax.
[0398] [Table 1]
[0399] [Table 2] [Explanation of symbols]
[0400] 1. Energy ray curable pressure sensitive composition precursor 2 Application roller 3 Metal roller 4 Recording media 5 Pressure roller 6 Conveyor belt 7 Tray 8 light source 9. Scraver 10 Photoconductor drum 10K Black Photoconductor 10Y Yellow photoconductor 10M Magenta photoconductor 10C Cyan photoconductor 14, 15, 16 Support rollers 17 Cleaning equipment 18 Image forming means 20 Charging roller 21 Exposure equipment 22 Secondary transfer device 23 Laura 24 Secondary transfer belt 25 Fixing device 26 Fixing belt 27 Pressure roller 28 Reversing device 30 exposure light 32 Contact Glass 33 First Running Body 34 Second Running Body 35 Imaging Lens 36 Reading sensor 42K, 42Y, 42M, 42C Developer storage unit 43K, 43Y, 43M, 43C Developer supply roller 44K, 44Y, 44M, 44C Developing roller 45K Black Developer 45Y Yellow Developer 45M Magenta Developer 45C Cyan Developer 49 Resist Roller 50 Intermediate transfer body 51 Lola 52 Corona charger 53 Manual feed path 55 Switching claw 56 Discharge roller 57 Output tray 58 Separation roller 60 Cleaning Equipment 61 Developer 62 Transfer roller 63 Cleaning Equipment 64 Static electricity removal lamp 70 Static electricity removal lamp 80 Transfer roller 90 Cleaning Equipment 95 Recording media 100A, 100B Image forming apparatus 120 Tandem type developer 130 Manuscript stand 142 Paper feed roller 143 Paper Bank 144 Paper feed cassette 145 Separation roller 146 Paper feed path 147 Transport roller 148 Paper feed path 150 Copying device body 151 Manual feed tray 200 Paper feed table 300 Scanner 400 Automatic document feeder L exposure light [Prior art documents] [Patent documents]
[0401] [Patent Document 1] Patent No. 6163943
Claims
1. a toner image forming step of forming a toner image on a recording medium using a toner; a coating step of coating an energy beam curable pressure-sensitive composition precursor on the recording medium on which the toner image is formed to form an energy beam curable pressure-sensitive composition precursor layer; a curing step of irradiating the recording medium on which the energy ray-curable pressure-sensitive composition precursor layer is formed with an energy ray to cure the energy ray-curable pressure-sensitive composition precursor layer to form an energy ray-curable pressure-sensitive composition; a pressure-bonding step of bonding the surfaces on which the energy ray-curable pressure-sensitive composition is formed together and bonding them together by a pressure-bonding means, In the toner image formed by the toner image forming process, the size of a flat area of the toner image measured by the following measurement method is 200 μm or less, the toner image forming step includes a transfer step of transferring a toner image on a photoconductor or an intermediate transfer body to the recording medium, and a fixing step of fixing the toner image transferred to the recording medium, The method for producing a removable information sheet, wherein the transfer step is performed by a transfer bias in which a DC bias is superimposed on an AC bias. <Measurement method> In the solid portion of the toner image, areas that are 2 μm or more deep from the surface are defined as recesses, and other areas are defined as flat portions of the toner image. A microscopic photograph of the solid portion of the toner image is obtained, the microscopic photograph is binarized, and circles are drawn within the flat portion of the toner image so as not to overlap the recesses. The diameter of the largest of the drawn circles is defined as the size of the area of the flat portion of the toner image.
2. 2. The method for producing a removable information sheet according to claim 1, wherein the pressing means presses the recording medium while heating it.
3. 3. The method for producing a removable information sheet according to claim 1, wherein the toner contains an ester-based wax.
4. In the fixing step, an oil-less fixing process is performed without using a lubricant, The method for producing a removable information sheet according to any one of claims 1 to 3, characterized in that the toner image obtained by the toner image forming process has a wax coverage of 40 to 70% as determined by the following measurement method. <Method of measuring wax coverage> A solid portion of the toner image is exposed to the saturated vapor pressure of an aqueous solution of ruthenium tetroxide, and then a backscattered electron image is obtained using an electron microscope. The backscattered electron image is binarized based on whether the brightness determined for each pixel is equal to or greater than a threshold value, and the ratio of the area of the black parts to the area of the entire binarized image is defined as the coverage rate of the wax.
Citation Information
Patent Citations
Assembling method of optical disk
JP1986063943A
Fixing device of image forming apparatus
JP2004264393A
Image forming apparatus, image forming method and process cartridge
JP2007322928A
Transfer device and image forming apparatus
JP2013127599A
Image forming method
JP2013152294A